Cooperative management reshapes seasonal nitrogen synchrony and surface-water nitrogen risk in pastoral regions - Tianyun Qi; Tianer Song; Mei Huang; Wenyin Wang; Binyu Luo; Shuai Qi; Cai’e Wang; Rong Rong; Lin Ma; Jianhui Xu; Tao Zhang; Yanfu Bai; et al. (Agriculture, Ecosystems & Environment, 2027)

Effects of equivalence ratio on vented H2/CH4/air explosions in the chamber with a hinged vent panel - Hongzhe Rong; Jialin Li; Jin Guo; Yiming Wang; Zhongrui Chen; Fuqiang Yang (Fuel, 2026)

From descriptive digital twins to closed-loop intelligent agents: Adaptive biogeochemical management in river-reservoir systems - Honghong Guo; Ruopu Yuan; Tongtong Wang; Rong Li; Yijia Li; Yuhang Su; Haihan Zhang; Tinglin Huang (Water Research, 2026)

Cropping diversification increases microbial network complexity associated with enhanced soil multifunctionality and resistance to global change - Qian Guo; Peng He; Rui Li; Rong Yang; Jianing Wang; Tengfei Ma; Ning Ling; Lina Zheng; Zhaoming Wang (Soil and Tillage Research, 2026)

Oral Janus nanomotor covalent conjugation rapeseed protein-derived DPP-IV inhibitory peptide and liraglutide: A self-propelled targeted delivery system for promoting insulin secretion and glucose-lowering - Huimin Dong; Haiyan He; Huizhen Xing; Chengzhi Guo; Zhigao Wang; Rong He (Food Research International, 2026)

Synergistic room-temperature NH3 sensing: TiO2/g-C3N4 heterojunction with UV-enhanced performance for food freshness monitoring - Haineng Bai; Chenjie Wang; Yang Yu; Yiru Chen; Cheng Feng; Yunxiao Du; Yamin Feng; Weifeng Liu; Kuili Liu; Sihua Zhou; Fuqiang Guo; Qingfeng Li; et al. (Chemical Engineering Journal, 2026)

Orders-of-magnitude reactivity enhancement in persulfate activation by curvature-dependent oxygenated carbon nanotubes - Xin Yang; Zhongyuan Guo; Pufan Wang; Justin Prabowo; Yangyang Wang; Jiaxiang Chen; Jiacheng Wu; Xinyi Huang; Yichen Feng; Chengli Rong; Fangzhou Liu; Hao Li; et al. (Chemical Engineering Journal, 2026)

Combined regulation of CO2 and nutrients on carbon fixation and emission of Microcystis aeruginosa: physiological and transcriptomic insights - Jiao Ran; Guo Li; Lijing Wang; Binghui Zheng; Ensheng Zhu; Rong Xiang; Shanyuan Xue; Zheng Zheng (Water Research, 2026)

A new antibacterial unsaturated fatty acid from Xisha coral-associated actinomycete Streptomyces sp. SHEa3 - Rong Wang; Shiquan Chen; Quanying Feng; Zhikai Guo; Qiuhua Mao (Phytochemistry Letters, 2026)

Recent advances in buckwheat (Fagopyrum Mill) polysaccharides: extraction and purification, structural characterization, and biological activities - Shunfeng Lan; Rong Ji; Lidong Guo; Haixue Kuang; Zhibin Wang (Food Chemistry, 2026)

Surface-engineered Au@Pt nanoparticles-based colorimetric/fluorescent dual-mode three-channel sensor array: Discrimination of light aroma-type Baijiu with variable qualities - Yukun Yang; Jian Liu; Rong Guo; Baoqing Bai; Tao Bo; Jinhua Zhang; Ligang Yu; Huilin Liu; Ying Zhang; Shuo Wang (Food Chemistry, 2026)

Integrated metabolomics and network pharmacology reveal metabolic remodeling and potential antioxidant mechanisms in fermented Lycium barbarum - Jianyu Huang; Dengmi Wang; Ziyi Yang; Jinrou Xie; Die die Wang; Rong Guo; Dunhua Liu; Song Miao; Jicheng Chen (Food Bioscience, 2026)

Molecular mechanisms of neutron irradiation damage in CL-20: A multiscale modeling approach from collision cascades to real-space defect mapping - Wei-Yi Li; Tao Wang; Rong Liu; Yu-Heng Li; Wan-Xiao Guo; Xi-Yao Yun; Yi-Lin Fang; Jin-Tao Wang; Ning Gao (Chemical Engineering Journal, 2026)

Persistent contamination, limited accumulation: In-situ isotope tracing reveals fast thallium turnover in natural waters - Chenghong Yu; Hongkai Wang; Wenze Xiao; Qiao-Guo Tan; Rong Chen; Lihua Liu; Nengwang Chen; Minwei Xie (Aquatic Toxicology, 2026)

Corrigendum to ‘Machine Learning-Driven Recombinant Xylanase Synergized with Pediococcus pentosaceus: Directed Xylose-Lactate Conversion and Metabolic Mechanism of Lignocellulosic Waste’[Resources, Conservation & Recycling 234 (2026) Article 109058] - Jiajin Sun; Yujuan Zhang; Luyao Zhang; Chen Shen; Yitong Lin; Rong Zhao; Lei Chen; Qiang Liu; Cong Wang; Wenjie Huo; Gang Guo (Resources, Conservation and Recycling, 2026)

Inoculation with phosphate-solubilizing bacteria reduce the transport of cadmium in Brassica napus L. by reshaping phosphate-solubilizing microbes in rhizosphere - Xiao Chen Zhang; Tong Yu Feng; Xiu Rong Tao; Lu Chen Wang; Jing Wen Kong; Yi Yao Mai; Yang Chen; Qing Guo; Long Guo; Chuan Jun Dai; Min Zhao (Rhizosphere, 2026)

Ambient PM2.5 exposure and sleep quality: Evidence from circadian DNA methylation signatures in a population-based study - Yuting Wang; Shuzhen Liu; Jiahui Rong; Yaxin Luo; Siyuan Niu; Peifeng Guo; Xu Tang; Yujian Liang; Xiaoting Mo; Linhai Zhao; Shiwen Jiang; Tiantian Gu; et al. (Journal of Hazardous Materials, 2026)

In-situ generation and activation of H2O2 by synergistic dipole moment and multi-metal cycle for piezo-photocatalytic water cleanup - Zheng-Tao Dong; Long Sui; You Wu; Xiao-Ju Wen; Ya-Ya Yang; Yan-Rong Chen; Wen-Jun Wang; Hai Guo (Chemical Engineering Journal, 2026)

Differential Environmental Response Patterns Between Spawning and Nursery Habitats of Coilia mystus in the Yangtze Estuary - Dong Wang; Xiangyu Long; Zengguang Li; Rong Wan; Tiejun Li; Yuanming Guo; Pengbo Song (Fishes, 2026)
Estuaries support distinct spawning and nursery habitats for migratory fishes, yet the differential environmental response patterns between these two critical early life habitats remain poorly understood from a spatial non-stationarity perspective. Based on six ichthyoplankton surveys conducted during peak and late spawning seasons from 2018 to 2020 in the Yangtze Estuary, this study applied geographically weighted regression (GWR) models to quantify the spatially varying effects of sea surface temperature, sea surface salinity, chlorophyll-a, water depth and distance to coast on the distributions of Coilia mystus eggs and larvae. The results reveal clear divergence in both spatial pattern and environmental drivers between spawning and nursery habitats. Spawning grounds were persistently concentrated in the middle reaches of the South Branch, and shifted approximately 10 km upstream during the spring saltwater intrusion event in 2020. Nursery grounds, by contrast, formed a stable dual-core structure, with the northern core at the North Branch mouth consistently supporting higher larval densities than the southern core in the North and South Passages. Salinity was the primary limiting factor for spawning in spring, while temperature dominated in summer, and chlorophyll-a was never retained in optimal egg models. For larvae, chlorophyll-a emerged as a consistent key driver alongside salinity and temperature, and local regression coefficients spanned a wider range than those for eggs, indicating greater spatial heterogeneity in larval distribution–environment relationships. This study provides the first comparative analysis of spatially non-stationary environmental controls on spawning versus nursery habitats of C. mystus, and offers empirical support for stage-specific habitat conservation and fisheries management in the Yangtze Estuary.

Phosphorus limitation and manganese toxicity induced by high nitrogen inputs suppress plant biomass - Jiapu Li; Xuebin Yan; Jordi Sardans; Josep Peñuelas; Shiting Hong; Peng Wang; Pinwei Zhang; Rong Song; Yanwen Zhao; Yong Li; Hui Guo (Plant and Soil, 2026)

Unsupervised Fault Segmentation Method Based on Geological Constraints - Hongjia Ren; Xu Guo; Yongcai Wang; Rong Chu; Qi Wang; Xihao Fan; Yougong Wang (Mathematical Geosciences, 2026)

Chemical and isotopic constraints on sources of precipitation chemistry in the Yangtze River Delta: A multi-year comparison of mountain and urban sites - Yongbin Jiang; Fei Rong; Guo Hu; Fuchao Zhou; Yanjun Huang; Xiaoyun Wang; Tao Huang; Tao Zhong (Acta Geochimica, 2026)

Retraction notice to “Algorithm developed for dynamic quantification of coal consumption for and emission from rural winter heating” [Sci. Total Environ. 737 (2020) 139762] - Yuzhe Zhang; Guorui Zhi; Sicong Guo; Wenjing Jin; Lei Wang; Jinhong Du; Miaomiao Cheng; Zhigang Xue; Yisheng Xu; Rong Shi; Yajing Lu; Hongyan Dang; et al. (Science of The Total Environment, 2026)

Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Machine learning-driven recombinant xylanase synergized with Pediococcus pentosaceus: directed xylose-lactate conversion and metabolic mechanism of lignocellulosic waste - Jiajin Sun; Yujuan Zhang; Luyao Zhang; Chen Shen; Yitong Lin; Rong Zhao; Lei Chen; Qiang Liu; Cong Wang; Wenjie Huo; Gang Guo (Resources, Conservation and Recycling, 2026)

Natural pyrite-enhanced co-culture system for simultaneous nitrate and ammonium removal under low C/N conditions: Mechanistic insights and real wastewater application - Kuang-di Xu; Pan He; Xiang-lin Liu; Lei Yu; Si-jia Li; Quan Wang; Rong-ping Chen; Ke Yin; Guang Guo; Wen-Jie Xu; Gong-De Wu (Bioresource Technology, 2026)

Refractory Dermatophytosis Caused by Trichophyton indotineae: A Case Series Highlighting Antifungal Resistance and Management Challenges - Yubo Ma; Rong Yan; Yakun Shao; Chunying Xiao; Tianshuo Zhao; Xingyu Li; Gang Wang; Chunying Li; Yinggai Song; Meng Fu; Yanyang Guo (Mycopathologia, 2026)

Dendrobium devonum juice modulates aroma formation in coffee cherry husks processing: insights into key pathways and flavour enhancement - Wenrui Huang; Zhiting Zhang; Jiawei Tang; Qinghua Chuai; Yinbo Wang; Rong Wang; Yongming Bao; Feng Guo (Food Additives & Contaminants: Part A, 2026)

Quantifying the light interception and canopy photosynthesis of strip intercropping system based on 3D canopy photosynthesis model - Si-Rong Huang; Qing-Feng Song; Zheng Guo; Qiu-Feng Long; Li-Sha Zhang; Yue Li; Yuan Yang; Xiao-Chun Wang; Feng Yang; Tai-Wen Yong; Jiang Liu; Yan-Hong Yan; et al. (Computers and Electronics in Agriculture, 2026)

Multidimensional effects of personalized exercise intervention in type 2 diabetes: a randomized controlled trial - Dan Liu; Di Cheng; Qinyi Wang; Ying Zhang; Piao Kang; Chufan Zhao; Hongfeng Mao; Jing Qu; Sheng Liu; Xiaojing Gao; Rui Han; Jingyi Guo; et al. (Science Bulletin, 2026)

Os79, a UDP‐Glycosyltransferase, negatively regulates cadmium tolerance and accumulation in rice - Rui Guo; Hao Yu Wang; Chong Wei Zhong; Rong Rong Ma; Jiu Huang; Jin Chen; Xian Jiao Guan; Lu Zheng; Ren Fang Shen; Ming Qing Liu; Xiao Fang Zhu (Journal of Hazardous Materials, 2026)

Interfacial engineering of 2D heterojunction with coordination bridging for efficient photocatalytic biomass upgrading - Taolian Guo; Rong Dang; Shaodan Wang; Anyu Zheng; Wu Chen; Chao Wang (Chemical Engineering Journal, 2026)

Molecular characterization of a novel partitivirus isolated from Fusarium solani, the causal agent of tobacco root rot - Xiao Wu; Ying Wang; Rui Guo; Ya Rong Wang; Si Jun Li; Xiang Ping Zhou; Jie Zhong; Yan Song Xiao; Tian Bo Liu (Archives of Virology, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Enhanced tellurium recovery via ultrasonic-assisted alkaline leaching-electrodeposition with integrated alkali regeneration - Su Yan; Shixing Wang; Libo Zhang; Rong Zhu; Xinrui Yang; Hongliang Liu; Jianqiang Ye; Guowei Luo; Yonggang Zuo; Gengwei Zhang; Guo Lin; Likang Fu (Chemical Engineering Journal, 2026)

Operational control mechanism and pilot-scale demonstration of integrated fixed-film activated sludge partial nitritation/anammox system - Zibin Luo; Chao Rong; Tianjie Wang; Yu Qin; Jiang Wu; Yan Guo; Yisong Hu; Zhe Kong; Taira Hanaoka; Shinichi Sakemi; Yu-You Li (Bioresource Technology, 2026)

CRISPR/Cas12a-mediated electrochemiluminescent biosensor integrating Ag modified Co-doped metal-organic frameworks for dual detection of malathion and phorate - Ying Zhang; Wenke Liu; Rong Guo; Yanli Qi; Baoqing Bai; Jinhua Zhang; Nan Hu; Ying Gu; Yukun Yang; Shuo Wang (Analytica Chimica Acta, 2026)

Soil organic carbon in arid and humid grasslands of China: Spatial heterogeneity, driving factors, and future changes - Zihan Kan; Mingming Wang; Jiyuan Liu; Shihang Zhang; Wei Hang; Boyi Song; Yongxing Lu; Hao Guo; Xing Guo; Jungang Yang; Xiaoying Rong; Ye Tao; et al. (Science of The Total Environment, 2026)

Boron fortifies a dual barrier in rice roots: How Casparian strip reinforcement and cell wall remodeling restrict cadmium entry - Zhihong Guo; Min Nie; Ting Li; Changfeng Ding; Gaoxiang Huang; Zhengfu Yue; Yurong Wang; Taolin Zhang; Rong Huang; Xingxiang Wang (Journal of Hazardous Materials, 2026)

A room-temperature wireless NO2 gas sensor enabled by WO3 modified V2CTx nanosheets - Haineng Bai; Rui Guo; Yixin Zhou; Cheng Feng; Yiru Chen; Shengjie Zhang; Yamin Feng; Weifeng Liu; Kuili Liu; Fuqiang Guo; Jin Wang; Dunjun Chen; et al. (Chemical Engineering Journal, 2026)

Metal-free C H functionalization unlocks multifunctional luminescent PEGs for biomedical imaging and therapy - Weiping Liu; Qinyue Guo; Lifang Ma; Ruohan Li; Jiajia Ren; Haixia Jiang; Gang Wang; Rong Zeng (Chemical Engineering Journal, 2026)

Mechanism of synergistic astringency enhancement by organic acids in model wine: Insights from organic acid-phenols-protein triadic interaction - Yan Liu; Xiang Jie Jiang; Shi qing Zhang; Qing hao Zhao; Yue fan Zhao; Wan Rong Zhao; Shi Yi Peng; Guo Rong Du; Xiao Yuan; Peng Tao Zhao; Xiao Yu Wang (Food Chemistry, 2026)

Highly efficient removal and detoxification of ochratoxin a in wine via adsorption-photocatalytic synergy of polymerized dopamine-wrapped magnetic titanium dioxide - Saiqun Wang; Keying Chu; Rong Guo; Yue Liu; Lu Cui; Zhouli Wang; Xubo Zhao (Food Chemistry, 2026)

Inactivation of microbial and pest contamination in post-harvest wheat by plasma-activated gas - Sihong Ma; Pengyu Zhao; Tianyi Song; Zhengyu Wang; Shenghang Xu; Li Guo; Zifeng Wang; Jishen Zhang; Hao Zhang; Dingxin Liu; Xiaohua Wang; Mingzhe Rong (Food Control, 2026)

Construction of mineral-carbon nanosheet using waste activated sludge and bentonite for boosting dye adsorption - Rong Guo; Lina Wang; Di Zhang; Chuanhui Jiang; Guoxiu Qian; Yonggang Wu (Environmental Research, 2026)

Monodisperse lutetium-177-labeled poly(lactic acid) microspheres for radioembolization therapy of hepatocellular carcinoma - Qing-Rong Jiang; Ping He; Ling-Yun Guo; Qi-Yi Mo; Xing-Long Zhou; Wei Wang; Zhuang Liu; Rui Xie; Da-Wei Pan; Wen-Jie Zhang; Xiao-Jie Ju; Liang-Yin Chu (Chemical Engineering Journal, 2026)

Cold adaptation strategies of anammox bacteria and the bottleneck of nitrogen removal performance in autotrophic nitrogen removal process treating digested swine wastewater - Ya-hui Wang; Fang-yu Huang; Long-xing Jiang; Rong You; Yun-hong Zhang; Liang-wei Deng; Wen-guo Wang; Lan Wang (Chemical Engineering Journal, 2026)

Pyrite-driven redox modulation improves microbial tolerance to furan inhibitors in hydrogen production from lignocellulosic hydrolysates - Hao-Yu Sun; Xin Xu; Si-Jia Li; Lei Yu; Quan Wang; Rong-Ping Chen; Ke Yin; Guang Guo; Xu Sun; Yu-ting Xin; Wen-jie Xu; Gong-De Wu (Bioresource Technology, 2026)

The emerging role of fatty acids as key bioactive components of Ganoderma lucidum spore oil in alleviating tumor progression - Qi-Jun Chen; Zi-Xuan Li; Guo-Cai Wang; Ting Xie; Guan-Di Xiao; Hui Xu; Jing Li; Xiang Luo; Yi-Fang Li; Lei Liang; Ju-Yan Liu; Yan-Ping Wu; et al. (Journal of Natural Medicines, 2026)

Transcriptomic exploration unveils hub genes influencing fatty acid composition across various sections of yak meat - Bo Hu; Haiyue Wu; Rong Hu; Zhongxin Yan; Lu Sun; Haijia Ren; Yahui Guo; Meisong Wang (Genes & Genomics, 2026)

Hydrogeophysical Imaging and Joint Interpretation of Rainfall Infiltration on an Embanked Slope in the Mid-Lower Yangtze Hilly Region - Rong-wen Guo; Chen-yang Li; Zhuo Liu; Deng-kang Wang; Ming Yu (Applied Geophysics, 2026)

Automatic Detection of Disaster-Causing Organisms near the Waters of Nuclear Power Plant Based on LiveScope Scanning Sonar Images - Gangyi Yu; Shuo Wang; Wei Liu; Yongjian Xia; Yuchen Guo; Xiaolu Chen; Xueping Wei; Ao Chen; Zehua Lv; Chao Lu; Junbo Zhang; Rong Wan (Journal of Marine Science and Engineering, 2026)
Nuclear power serves as an efficient, clean, and low-carbon energy source that constitutes a significant component of the energy portfolio in numerous countries. Most nuclear power plants are predominantly situated in coastal regions, utilizing seawater as the ultimate heat sink for their cooling systems. Real-time monitoring of marine organism dynamics near water intakes is essential to mitigate the risk of unit shutdowns triggered by outbreaks of disaster-causing organisms (DCOs). This study employed LiveScope scanning sonar videos captured near the Ningde Nuclear Power Plant to develop a dataset for detecting the light spot area of the DCOs. We proposed a directionally optimized model, Bio-YOLO v7, which significantly enhances the detection of small targets in sonar images. The Bio-YOLO v7 model achieved precision, recall, and average precision rates of 85.29%, 83.28%, and 81.49%, respectively, demonstrating superior performance in identifying DCOs near the intakes of nuclear power plant. The light spot size of the DCOs exhibited significant periodic variations, serving as a crucial indicator for forecasting outbreak events.

Physical properties as the key bridge from structure-activity relationship to AI-guided rational design of food-derived bioactive peptides: A systematic review - Huizhen Xing; Huimin Dong; Chengzhi Guo; Zhigao Wang; Rong He (Trends in Food Science & Technology, 2026)

Synergistic effects of climate forcings from three oceans on the reserve of “Atmospheric water tower” over the Tibetan Plateau - Pengjie Ren; Wusheng Yu; Stephen Lewis; Yaoming Ma; Yuanyuan Dang; Lei Zhong; Zhuanxia Zhang; Yong Liu; Lun Luo; Zhaowei Jing; Jingyi Zhang; Rong Guo; et al. (Journal of Hydrology, 2026)

Short-term black carbon exposure impairs mental health and DNA methylation signatures of mitochondrial carrier genes - Shuzhen Liu; Yaxin Luo; Jiansheng Cai; Yuting Wang; Jiahui Rong; Xiaoting Mo; Yujian Liang; Zeyan Ye; Xu Tang; Siyuan Niu; Tiantian Zhang; Lei Luo; et al. (Journal of Hazardous Materials, 2026)

Impacts of iron additives on enzymatic activities and nitrogen cycling during composting: Microbial and biochemical insights - Yang Wang; Hong-Yi Wu; Shuang-Yan Jia; Hao-Duo Bai; Kuok Ho Daniel Tang; Xiu-Na Ren; Zhixin Zhang; Yao Yiqing; Guo Xiaohui; Chugang Mei; Rong-Hua Li (Journal of Cleaner Production, 2026)

Unlocking a new application of coal and biomass co-ethanolysis: high-performance supercapacitor based on N/O self-doped hierarchical porous carbons - Li Li; Yu-Fan Ren; Chang-Wang Shao; Long-Yu Zhang; Guo-Rong Qi; Xing-Shun Cong; Xian-Yong Wei; Zi-Chun Fan; Xiao-Yu Zhang (Fuel, 2026)

Optical diagnostic study on the combustion and soot formation process of nanobubble diesel - Han Wang; Liang Guo; Wanchen Sun; Yuying Yan; Hao Zhang; Miao Yang; Mengqi Jiang; Degang Li; Rong Xuan; Junfeng Zhang; Kaiqi Yang (Fuel, 2026)

Tailoring a simplified and steady-state kombucha consortium for newly-formulated kiwifruit beverage production: Impacts on untargeted/targeted metabolites, antioxidant capacities and flavor profiles - Shiqi Li; Keying Chu; Rong Guo; Jiamin Wu; Xingnan Wang; Jing Guo; Yahong Yuan; Tianli Yue; Rui Cai; Zhouli Wang (Food Research International, 2026)

Rice bran protein-based self-propelled nanomotors for targeted delivery of dihydroquercetin: A food-grade nano-system for anti-atherosclerosis - Huizhen Xing; Huimin Dong; Chengzhi Guo; Yucheng Zou; Zhigao Wang; Xiaohu Luo; Rong He (Food Research International, 2026)

Constructing a core-shell heterojunction with photo-activated antifouling shield via interface engineering for uranium extraction from water - Yue Ma; Yilei Zhang; Huazhen Rong; Jinjiao Pan; Chuan Gan; Zhuoming Yang; Yu Guo; Yihui Yuan; Ning Wang (Desalination, 2026)

Dual efficient X-ray scintillation and strong second harmonic generation in a single cubic alkane Cu4I4 cluster achieved through organic-inorganic synergistic effect - Bao-Yi Li; Jun-Zhe Li; Wen-Fei Wang; Peng-Kun Wang; Rong Li; Shuai-Hua Wang; Fa-Kun Zheng; Guo-Cong Guo (Chemical Engineering Journal, 2026)

Boosting surface basicity of In2O3 aerogel for high-performance H2S sensors via an in-situ annealing strategy of carbon-composited In(OH)3 - Zheng Yang; Qian Rong; Wei Zhang; Qi Xu; Mengen Shao; Jiang Li; Chunchang Wang; Youmin Guo (Chemical Engineering Journal, 2026)

Low-δ18O magmas at Batur, Indonesia: Evidence for slab-window melting beneath arc volcanoes - Guo-Rong Tang; Wei Dan; Adi Maulana; Jian Wang; Xiu-Zheng Zhang; Xin Ma; Qiang Wang; Xi-Jun Liu; Gong-Jian Tang (Chemical Geology, 2026)

Incorporating Ecoregions and Freeze–Thaw Effects Effectively Improves the Accuracy of Machine Learning Models for Baseflow Prediction in Seasonally Frozen Regions - Tingting Deng; Hang Lyu; Rong Zhong; Yunting Zou; Jianan Wang; Yu Li; Yue Guo (Water Resources Management, 2026)

Plant-soil feedback driven by root-associated fungal communities accelerates the secondary succession of bare saline-alkaline grassland patches - Xiaona Zheng; Yuhong Yin; Dan Yang; Jingjuan Bi; Wenlong He; Siya Li; Xiao Liang; Jigui Chen; Rong Wang; Zhiying Guo; Xing Li; Tao Zhang; et al. (Plant and Soil, 2026)

Modeling the comparative evaluation of diverse washing agents for remediation of composite heavy metal-contaminated soil - Weijiang Huang; Bomin Xu; Minghua Yang; Rong Zhang; Weiping Zhang; Ning Wang; Ping Guo; Shaoyun Pu (Modeling Earth Systems and Environment, 2026)

Fatal infection of a novel canine/human reassortant H3N2 influenza A virus in the zoo-housed golden monkeys - Xia Wen; Rong Chen; Yingjun Lv; Jinzhu Geng; Jingjing Guo; Yaru Sun; Aohan Yang; Yuhao Dong; Meirong Li; Changlin Deng; Guodong Wang; Yongjie Liu (Veterinary Microbiology, 2026)

Magnesium deficiency limits electron transport efficiency and photosynthesis, and induces oxidative stress in tobacco - Rong-Rong Xie; Jingjuan Gao; Changzheng Wu; Jinping Guo; Qian Cheng; Hailu Wang; Tinmin Liang; Jianjun Lu; Chaoyuan Zheng; Liangquan Wu; Li-Song Chen; Songbiao Chen; et al. (Plant Science, 2026)

Targeted interception of membrane foulants in MBR: A straw-microplastic composite adsorbent for effective removal of oil and biopolymeric contaminants from catering wastewater - Rong Zhang; Beiyu Xin; Cong Zhang; Xiaozheng Ma; Ruoxin Wang; Jifeng Guo (Journal of Hazardous Materials, 2026)

Investigating the Therapeutic Efficacy of Quality-Controlled, miR-146a-5p-Enriched Small Extracellular Vesicles Derived From MSCs Against Idiopathic Pulmonary Fibrosis - Xin Wang; Lingjiao Meng; Qiuhong Wang; Ruixue Rong; Yu Zhang; Xiaohui Zhao; Chen Liang; Huizhen Guo; Li Deng; Zengqi Tan; Feng Guan; Yi Tan (Stem Cell Reviews and Reports, 2026)
Small extracellular vesicles derived from umbilical cord mesenchymal stem cells (UC-sEvs) may be used for the treatment of idiopathic pulmonary fibrosis (IPF) because of their ability to control inflammation and inhibit fibrosis. However, the lack of clarity regarding the treatment mechanism of IPF and the corresponding quality standards limit the clinical application of these small extracellular vesicles. Here, we established a good manufacturing practice (GMP) grade process for isolating UC-sEvs, and RNA-seq was performed to screen for potential therapeutic cargo in the product to confirm the therapeutic effect of nebulized UC-sEv agents against IPF. Functionally, UC-sEvs inhibited the pulmonary inflammatory response by regulating macrophage function, thereby suppressing the bleomycin toxicity-induced progression of fibrosis. Mechanistically, miR-146a-5p enrichment in UC-sEvs may be involved in alleviating bleomycin-induced IPF by targeting TRAF6/IRAK1 to negatively regulate inflammation. The proposed quality control strategy ensures the stability of the product across three batches, with RNA-seq analysis revealing highly similar miRNA expression profiles. The feasibility of using miR-146a-5p as a key therapeutic molecule has been validated. Finally, on the basis of the results of pharmacodynamics and key therapeutic molecule studies, we provided a detailed quality control standard for IPF therapy by nebulizing UC-sEv. These findings help understand how sEvs impact IPF and the possible consequences of their therapeutic usage and offer a quality standard reference. Graphical Abstract

Screening of Fecal Bacteroides Strains and Discovery of Bacteroides eggerthii S13-F8 with Protective Effects Against Chemotherapy-Induced Diarrhea - Yi Zhao; Zhengqun Dai; Yanmei Lang; Rui Li; Hongyu Zheng; Jiajia Mi; Xiu He; Jin Liu; Rong Xiang; Xueran Mei; Yang Liu; Yantang Wang; et al. (Probiotics and Antimicrobial Proteins, 2026)

Astrocyte-Derived CXCL10 Induces Neuronal Tau Hyperphosphorylation and Cognitive Impairments in Sepsis - Cuiping Guo; Hang Ruan; Wensheng Li; Yi Liu; Abdoul Razak Yacoubou Mahaman; Qian Guo; You Zhou; Rong Liu; Jianzhi Wang; Chenliang Zhou; Xiaochuan Wang; Shusheng Li (Neuroscience Bulletin, 2026)

Echinacoside Improves Memory Function and Bone Mineral Density in the Aged SAMP8 Mouse Model - Rong Zhou; Ge Tian; Jing Yu; Rui Wang; Ning Peng; Xingzhi Guo; Rui Li (Molecular Neurobiology, 2026)

Performance of blood biomarkers in internal jugular vein for Alzheimer’s disease pathologies: the Delta Method study - Jun Wang; Dong-Yu Fan; Shan Huang; Chang Liu; Pei-Wen Zhao; Nan Wu; Xiao-Lin Gao; Qing-Zhi Wang; Yanli Li; Bai Liu; Yuan-Ye Ma; Rong-Chang Zhao; et al. (Science Bulletin, 2025)

A Bayesian network approach to cognitive alignment and trust in human–unmanned ship collision avoidance - Jian Zheng; Yicong Guo; Wuyue Rong; Wei Zhou; Xinlong Wang; Xucun Qi (Ocean Engineering, 2025)

Hydrodynamic characterization and efficient prediction of tapered trash-blocking nets for coastal nuclear intakes: Integration of experiment, simulation, and machine learning - Shaojian Guo; Nan Gu; Cheng Zhou; Liwen Liu; Rong Wan; Yucheng Wang; Zhiqiang Liu (Ocean Engineering, 2025)

Pelletization and steam reactivation of steel slag-derived calcium-based sorbent for CO2 capture - Nai Rong; Yuhan Wang; Zhihang Guo; Kaiwei Liu; Xiuliang Shi; Long Han; Lichao Ge; Geng Wang; Chao Hu; Xiaokang Wan (Journal of Environmental Chemical Engineering, 2025)

Development and validation of a magnetic - based corrosion detection system for reinforced concrete structures - Jian Cheng; Yu-meng Xie; Rong-sen Gao; Ye Tian; Guo-yi Zhang; Dongming Yan; Bo Chen; Ruo-yi Zhao; Bei Li; Jun Chen; Dong-yang Cai; Wei-qiang Wu; et al. (Engineering Structures, 2025)

Nanoengineered polymeric RNA nanoflowers for dual-pathway modulation and effective therapy for non-small cell lung cancer - Li Wang; Dongbin Guo; Yifei Shan; Luanbiao Sun; Rong Wang; Bingmei Wang; Jiyu Guan; Quan Liu; Runze Li; Changfeng Zhu; Yicheng Zhao (Chemical Engineering Journal, 2025)

Trio‐WES and functional validation reveals a novel splice site variant of SLC26A3 in a case with congenital chloride diarrhea and a systematic review of SLC26A3 mutations in China - Ruixue Zhang; Hongping Li; Rong Qiang; XinRu Gao; Jinzhen Guo; Guoqiang Chen; Qin Nan; Limei Zhong; Lin Wang (Molecular Genetics and Genomics, 2025)

Lithospermic acid targeting heat shock protein 90 attenuates LPS-induced inflammatory response via NF-кB signalling pathway in BV2 microglial cells - Jie Guo; Chen-guang Li; Feng-yi Mai; Jing-rong Liang; Ze-hao Chen; Jiao Luo; Ming-chao Zhou; Yu-long Wang; Wen-tao Yang (Immunologic Research, 2025)

Limonoids and protolimonoid from Swietenia macrophylla - Yun-Peng Sun; Wen-Fang Jin; Ze-Rong Xu; Ying-Wei Liu; Li-Juan Sun; Yang Yu; Jin-Song Liu; Guo-Kai Wang (Natural Product Research, 2025)

Caulerpin suppresses tumor-associated angiogenesis and tumor growth via Hippo signaling in cervical cancer - Guang Yang; Yan Mo; Honghong Rong; Bihui Guo; Qingbing Zha; Hanli Shuai; Minghua Wang; Ping Li (Toxicology and Applied Pharmacology, 2025)

Non-extractable residues as the dominant fate of bisphenol A (BPA) in oxic paddy soil: formation and characterization - Yanan Zhao; Yongfeng Wang; Xiaoran Guo; Siqi Cao; Bingqi Jiang; Yao Yao; Xiaolong Liang; Rong Ji (Science of The Total Environment, 2025)

Biosynthetic rule-guided theoretical chemical space mapping strategy for enhanced analysis of plant metabolomes: application to the geographical profiling of goji berry - Wan-Yang Sun; Zhi-Hui Luo; Jie-Qi Cai; Qian Guo; Guo-Tao Chen; Guo-Dong Chen; Dan Hu; Hai-Guang Gong; Xue Li; Wei Bi; Ying Wang; Kwok-Fai So; et al. (Science Bulletin, 2025)

A BrDof2.4-BrHDA6 module is involved in ABA-CTK-mediating leaf yellowing in Chinese flowering cabbage by affecting histone H3 and H4 acetylation of CCGs - Zhen-liang Mou; Lei Yan; Zong-li Liu; Xin-guo Su; Ze-xiang Zeng; Yuan Rong; Wei Shan; Jian-fei Kuang; Wang-jin Lu; Jian-ye Chen; Wei Wei; Jia Si (Postharvest Biology and Technology, 2025)

Iridoids and other constituents from the aerial parts of Patrinia rupestris and their inhibitory effects on nitric oxide production - Zhi-Yuan Liu; Sheng-Run Guo; Jian-Xian Tang; Chun-Yan Zhao; Li Pu; Li-Zhong Wang; Dan Liu; Rong-Tao Li; Hong-Mei Li (Phytochemistry, 2025)

Spatial distribution and chemical characteristics of bastnäsite and monazite provide insights into the Bayan Obo deposit, the world's largest rare earth element mineralization - Jin Wang; Lin Li; M. Santosh; Guo-Ying Yan; Jun-Feng Shen; Mao-Wen Yuan; Masroor Alam; Zhao-Jing Wang; Sheng-Rong Li (Lithos, 2025)

Carbon-ferric based coagulants for enhanced removal of turbidity, bisphenol A, and tetracycline from synthetic wastewater - Jean Claude Hakizimana; Yongkang Ye; Fang Zhang; Pamphile Ndagijimana; François Nkinahamira; Fidele Dusangumukiza; Hongwei Rong; Jingying Wang; Baihui Cui; Dabin Guo (Journal of Water Process Engineering, 2025)

Wireless gas sensor based on monolayer Ti3C2Tx-modified GaN/CuO heterostructures for ultrafast and trace detection of NO2 gas - Haineng Bai; Cheng Feng; Rui Guo; Yiru Chen; Wenfeng Yuan; Yunxiao Du; Yamin Feng; Weifeng Liu; Kuili Liu; Fuqiang Guo; Jin Wang; Dunjun Chen; et al. (Chemical Engineering Journal, 2025)

Artificial intelligence-guided fermentation process regulation reveals metabolic rewiring in gentamicin C1a overproduction - Feng Xu; Lihuan Su; Yuan Wang; Hao Gao; Kaihao Hu; Rong Ben; Yuanxin Guo; Xu Li; Ju Chu; Xiwei Tian (Bioresource Technology, 2025)

Breaking through the bottleneck of nitrogen pollution control in micropolluted water sources: Enhancement of aerobic denitrification efficacy driven by microbial community enrichment and its sustainable application - Honghong Guo; Yuhang Su; Shuhong Xue; Na Li; Rong Li; Sen Wang; Jianwei Bu; Haihan Zhang; Tinglin Huang (Water Research, 2025)

Decarbonization pathways and key emission drivers in ports: A scenario-based study of Shanghai Port - Rong Shi; Yue Chen; Shuxia Yang; Xiaopeng Guo; Xiongfei Wang (Sustainable Cities and Society, 2025)

Multidimensional synergistic management of acid mine drainage: Constructing closed-loop technological systems bridging contamination control and resource circulation - Zhuang Ma; Lihong Zhou; Sen Wang; Shuai Zhu; Zeze Zhao; Rong Li; Tongtong Wang; Honghong Guo (Journal of Water Process Engineering, 2025)

Tracing toxic pollutants in coastal urban atmosphere: A case study on the particle-size distribution, sources, and health risks of PCDD/Fs, PCBs, PAHs, and substituted PAHs - Zhangpeng Guo; Shuai Sun; Rong Cao; Nan Jiang; Naibing Liang; Zichen Wang; Jiasen Guo; Minzhen Li; Xing Liu; Ningbo Geng; Jiping Chen (Journal of Hazardous Materials, 2025)

FT-ICR MS and viral metagenomics reveal distinct mechanisms of lysogenic and lytic phage-driven DOM transformations in wastewater at formula-levels - Qi Wang; Jieqi Tian; Rong Zhang; Pengcheng Yan; Yali Niu; Guodong Zhang; Qiuling Ma; Jian Zhou; Ruigang Wang; He Guo; Tiecheng Wang (Chemical Engineering Journal, 2025)

A ZnO packaged MEMS hydrogen sensor for reliable SIBO breath analysis with anti-H2S interference - Zheng Yang; Qian Rong; Wei Zhang; Xintao Fan; Mengen Shao; Jiang Li; Chunchang Wang; Youmin Guo (Chemical Engineering Journal, 2025)

Residual polyacrylamide-induced membrane fouling in short-flow coagulation-ultrafiltration: Behavior and mechanism - Mohan Wei; Yaozhong Zhang; Xing Zheng; Chi Zhang; Jiheng Duan; Kai Guo; Menghan Wang; Dongfei Li; Tianshuo Huang; Rong Chen (Chemical Engineering Journal, 2025)

The development of biological soil crusts shifts the drivers of soil multifunctionality in drylands - Mingming Wang; Boyi Song; Benfeng Yin; Ye Tao; Jing Zhang; Xiaoying Rong; Yonggang Li; Shihang Zhang; Zihan Kan; Yongxing Lu; Hao Guo; Xing Guo; et al. (CATENA, 2025)

One-pot construction of monodisperse core-shell silica microsphere with quinine-containing hybrid fibrous shell for racemates separation - Chenyang Wang; Tiantian Guo; Rong Li; Shujuan Ma; Yinmao Wei; Junjie Ou (Analytica Chimica Acta, 2025)

Male and Female Parent Birds Enhance Their Reproductive Success Using Different Strategies but the Same Optimal Pathway - Ning‐Ning Sun; Bi‐Yun Jia; Rong‐Yu Xu; Li‐Fang Gao; Xue‐Fei Guo; Rang Li; Yu‐Jie Wang; Shu‐Min Wang; Bo Du (Molecular Ecology, 2025)
Parental birds exhibit diverse alternative reproductive strategies; however, the pathways by which these alternative strategies enhance the reproductive success of parents remain poorly understood. Here, we used generalised linear mixed models (GLMMs) and structural equation modelling (SEM) to analyse a long‐term dataset of multiple components of reproductive fitness in the azure‐winged magpie ( Cyanopica cyanus ), including incipient offspring number, extra‐pair fertilisation (EPF), unhatched eggs, offspring preyed on by predators and conspecific raiders and offspring that starved. GLMM results revealed significant associations between these components and the first lay date. SEM further elucidated causal relationships among female/male breeding conditions, cooperative breeding, first lay date and the positive/negative effects on female/male reproductive success. SEM results revealed that both female and male reproductive success were mainly influenced by negative effects rather than positive effects. Specifically, negative effects were largely determined by unhatched eggs for females but by female EPF frequency for males. In contrast, positive effects were predominantly determined by the incipient offspring number for both sexes. Therefore, minimising negative effects was prioritised over enhancing positive effects to achieve reproductive success in both sexes. To modulate these effects, females and males employed different strategies. However, they achieved their respective goals through a shared pathway: reducing negative effects for social bonds formed with smaller‐bodied males and enhancing positive effects for social bonds formed with larger‐bodied males. Our multivariate analysis of various aspects of avian reproduction suggests that the formation of social bonds plays a more important role than alternative reproductive strategies in determining individual reproductive success.

Effects of aged microplastics on the abundance of antibiotic resistance genes in oysters and their excreta - Yifang Yu; Jing Qian; Weichao Wang; Minwei Xie; Qiao-Guo Tan; Rong Chen (Marine Environmental Research, 2025)

In Situ isotope tracing for metal bioaccumulation in open waters: Implications for interpreting biomonitoring data and safe seafood aquaculture - Haiyan Xiong; Tao Wang; Xue Cao; Jing Qian; Stuart L. Simpson; Rong Chen; Qiao-Guo Tan; Minwei Xie (Journal of Hazardous Materials, 2025)

Enhanced removal of high-temperature industrial particles via optimized spray droplet collision: Mechanisms and parametric control - Shengnan Guo; Yanqiu Huang; Yi Wang; Songheng Wu; Zhubin Wang; Junhao Rong (Journal of Hazardous Materials, 2025)

The evolutionary history of the Methyltransf_FA domain and its role in JH signal in silkworm, Bombyx mori - Chunyang Wang; Yang Yu; Qi Shen; Rong Xiong; Meiwei Guo; Jiamei Zhao; Dongsheng Yan; Rongcheng Zhang; Ping Chen (Insect Biochemistry and Molecular Biology, 2025)

Unraveling the diversity of bile acid modifications by integrative mass spectrometry approaches - Nan Xing; Yu-Fei Wang; Xue Ding; Hong-Li Tan; Yi-Fang Li; Guo-Xiang Sun; Rong-Rong He; Wan-Yang Sun (Science China Life Sciences, 2025)

Synergistic antimicrobial effect and mechanism of enterocin Gr17 and cinnamaldehyde against Escherichia coli and Candida albicans - Wen-yu Ma; Kai-sheng Shen; Zhao Wang; Qi Liu; Xin-jie Diao; Guo-rong Liu (Archives of Microbiology, 2025)

Spatio-temporal variations in the supply and demand of ecosystem services with multi-scenario prediction in Guangzhou City, China - Jun Wu; Zhi-Yun Jiang; Yan-Yu Xu; Lin Lin; Rong Guo; Yi-Jia Wang (Environmental Science and Pollution Research, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Isolation of pentasaccharide resin glycosides from the whole plants of Ipomoea biflora and their cytotoxic activities - Jin-Ping Gu; Tian-Zi Qi; Dong-Rong Zhu; Xu-Jia He; Su-Peng Guo; Xin Lan; Hong Gu; Jia-Lie Luo; Min Yang; Yu-Cheng Gu; Wen-Li Wang; Guang-Tong Chen; et al. (Phytochemistry, 2025)

Elimination of antibiotic resistance genes and adaptive response of Firmicutes during chicken manure composting - Wei-Li Jia; Ben Wang; Lu-Kai Qiao; Fang-Zhou Gao; Wang-Rong Liu; Liang-Ying He; Guang-Guo Ying (Journal of Hazardous Materials, 2025)

Dose-response pattern of marine macroalgae Gracilariopsis heteroclada to three fluoroquinolones and the cause-effect relationship of dose, growth, toxicity and sorption - Kun Lin; Youyou Guo; Rong Xin; Enyi Xie; Xuefeng Wang; Jianjun Cui; Jinhui Wu; Zhaowei Huang; Yong Liu; Shaoliang Lyu; Sipan Wang; Yongjian Huang; et al. (Algal Research, 2025)

Blocking secretion of exosomes by GW4869 dampens CD8+ T cell exhaustion and prostate cancer progression - Jing Liu; Hongyan Guo; Shiqi Liu; Yinying Hu; Yanqin Huang; Jiping Rong; Fang Yuan; Ruping Wang; Zhigang Wang (Human Cell, 2025)
Functional exhaustion of T lymphocytes is considered an important factor in the failure of tumor treatment. Accumulating evidence has shown that tumor cells cultivate their immune microenvironment through secreting exosomes. However, the mechanism through which tumor cell-derived exosomes participate in the regulation of lymphocyte function remains unclear. In this study, we found that exosomes derived from prostate cancer (PCa) cells were able to upregulate the expression of PD-1 and TIM-3 in CD8 + T cells, inducing the secretion of cytokines related to T cell exhaustion and significantly decreasing the ability to kill PCa cells. Importantly, our data indicated that treatment with GW4869 could reverse the effects of PCa-derived exosomes on CD8 + T cells and further inhibit the growth of PCa cells in vivo and in vitro by blocking the generation of exosomes. Our findings support the notion that exosomes derived from PCa cells can induce T cell exhaustion and promote PCa progression, while treatment of GW4869 effectively rejuvenates CD8 + T cells and reverses the effect of PCa exosomes. These findings indicate that GW4869 has potential in the treatment of PCa.

Direct recovery of high-purity uranium from fluoride-containing nuclear wastewater via extraction materials with ensemble Lewis sites and a tandem electrochemical device - Guo Li; Yan Liu; Chi Jiao; Zhengyu Jiang; Juan Zhang; Tao Chen; Tao Lin; Rong He; Wenkun Zhu; Xiangke Wang (Water Research, 2025)

Exploring morphological heterogeneity of circulating tumor cells: machine learning-based approach for cell identification and prognostic implications - Peng-Xiang Wang; Yu-Chen Zhong; Bin Duan; Jian-Wen Cheng; Yun-Fan Sun; Wen-Jing Zheng; Kai-Qian Zhou; Yang Xu; Hai-Xiang Peng; Wei-Xiang Jin; Hai-Min Li; Xiao-Juan Sun; et al. (Science Bulletin, 2025)

Genome-wide identification reveals a bZIP transcription factor modulating chlorophyll catabolism during leaf yellowing in harvested Chinese flowering cabbage - Ze-xiang Zeng; Yuan Rong; Zhong-qi Fan; Xin-guo Su; Lin Chen; Yan-chao Han; Hang-jun Chen; Wei Wei; Wei Shan; Jian-fei Kuang; Wang-jin Lu; Jian-ye Chen (Postharvest Biology and Technology, 2025)

Significant insights of CaO2 promoting heavy metal complexes removal during a plasma process - Meiqian Lu; Rong Li; Zichen Wang; Yue Liu; Guodong Zhang; Qiuling Ma; Jian Zhou; He Guo; Tiecheng Wang (Journal of Environmental Management, 2025)

Rapid and efficient nitrogen removal by a novel heterotrophic nitrification-aerobic denitrification bacteria Marinobacterium maritimum 5-JS in aquaculture wastewater: Performance and potential applications - Fu-Rong Wang; Shi-Yu Feng; Shuai Liang; Wei-Yu Du; Long-Qi Wang; Yu-Wei Zhang; Jia-Yu Ren; Shuang Gao; Yu-Jie Zhu; Yu-Ting Cong; Li Wang; Jing Gu; et al. (Environmental Research, 2025)

Hydrodynamic perturbations on contaminant behavior in low-permeability sediments: porewater metal dynamics and risk assessment implications - Ning Wang; Hongwei Hu; Wenze Xiao; Qiao-Guo Tan; Rong Chen; Minwei Xie; Stuart L. Simpson (Environmental Pollution, 2025)

Machine learning-driven molecular generation for accelerated screening of high-performance flame retardants in epoxy resin composites - Zhongwei Chen; Chunlei He; Kai Wang; Feng Rong; Long Xiang; Ziwei Zuo; Changliang Wang; Xinyuan Yang; Yong Guo; Juncheng Jiang; Yuan Yu (Chemical Engineering Journal, 2025)

A dual-blockade strategy targeting biochemical and biomechanical immune checkpoints to enhance tumor immunotherapy - Xiang Lu; Rong Guo; Mingjin Wang; Lifang Sun; Zhihui Song; Zhenzhong Zhang; Binghua Wang; Hongling Zhang (Chemical Engineering Journal, 2025)

Corrigendum to “Stable isotope tracing reveals glucose metabolism characteristics of drug-resistant B-cell acute lymphoblastic leukemia” [Analytica Chimica Acta 1352 (2025) 343884] - Rong Hu; Zhengwei Duan; Mengyao Wang; Mengting Liu; Yaoxin Zhang; Yanxi Lu; Yuhan Qian; Enjie Wei; Jianghua Feng; Pengfei Guo; Yang Chen (Analytica Chimica Acta, 2025)

Fragmentation pattern-based nontargeted screening strategy uncovered novel halogenated nucleotides in drinking water - Guangrong Sun; Pei Guo; Rong Liu; Han Yeong Kaw; Wei Wang (Journal of Hazardous Materials, 2025)

Enhancing functional metabolites and antioxidant activity of a novel alternative kombucha-like beverage: Tailor-made symbiotic microbial consortium for apple juice fermentation - Shiqi Li; Rong Liu; Zhihuan Jing; Yaodong Guo; Zhouli Wang (Food Bioscience, 2025)

Hydrolytic degradation of nerve agent simulants accelerated by host-guest gold nanozymes - Qingqing Sun; Mengyuan Wang; Qingqing Wen; Haili Dong; Yanchao Lyu; Jie Han; Rong Guo (Chemical Engineering Journal, 2025)

SIRT3 deficiency reduces PFKFB3-driven T-cell glycolysis and promotes arthritic inflammation - Ting-Ting Wang; Taotao Han; Xinyue Xiao; Dan Guo; Xin Sun; Yudong Liu; Lidan Zhao; Haojie Xu; Rong Li; Lingjuan Jiang; Bo Zhang; Beidi Chen; et al. (Science China Life Sciences, 2025)

Effects of polystyrene microparticles exposures on spermatogenic cell differentiation and reproductive endpoints in male mice - Rong Shen; Peng Xia; Yanan Guo; Pengfei Ji; Xinyi Yuan; Lu Wang; Si Shuang; Liwei Zhou; Ruizhi Tong; Lijuan Zhang; Disheng Liu; Degui Wang (Environmental Pollution, 2025)

Ultrafast self-gelling, superabsorbent, and adhesive chitosan-based hemostatic powders for rapid hemostasis and wound healing - Ashuang Liu; Shengyong Cui; Lei Song; Xiangshu Guo; Zhimao Huang; Shancan Wang; Kai Cheng; Ying Xiao; Youfen Fan; Rong Wang (Carbohydrate Polymers, 2025)

Prevalence of malnutrition among adult inpatients in China: a nationwide cross-sectional study - Yan Liu; Chunhua Song; Xue Wang; Xianghua Ma; Pianhong Zhang; Gaiyun Chen; Zhenqian Cheng; Juying Liu; Ying Yao; Wenjun Ma; Zengning Li; Ping Sun; et al. (Science China Life Sciences, 2025)

Stable isotope tracing reveals glucose metabolism characteristics of drug-resistant B-cell acute lymphoblastic leukemia - Rong Hu; Zhengwei Duan; Mengyao Wang; Mengting Liu; Yaoxin Zhang; Yanxi Lu; Yuhan Qian; Enjie Wei; Jianghua Feng; Pengfei Guo; Yang Chen (Analytica Chimica Acta, 2025)

Unlocking China's grain yield potential: Harnessing technological and spatial synergies in diverse cropping systems - Zhen-Zhong Dai; Sen Chang; Guo-Rong Zhao; Jia-Jia Duan; Hao-Yuan Liang; Zhi-Yuan Zhu; Sheng-Li Liu; Yong-Zhong Feng; Xing Wang (Agricultural Systems, 2025)

Temporal Dynamics of Genetic Diversity in Protected and Unprotected Wild Rice ( Oryza rufipogon ) Populations: Implications for Conservation - Zhi‐Zhou He; Wen‐Wen Shao; Olivier Honnay; Hui Liao; Hao Chen; Jing Liu; Shan‐Shan Dong; Ding Li; Guo‐Zhen Fan; Yao Zhao; Jun Rong; Yan Liu; et al. (Molecular Ecology, 2025)
Genetic diversity is vital for population survival, yet there is a paucity of studies focusing on the effectiveness of establishing protected areas for maintaining the population genetic diversity of threatened plant species. To evaluate the effectiveness of in situ conservation measures, we used simple sequence repeats (SSR) and single nucleotide polymorphisms (SNP) markers to monitor temporal dynamics in genetic diversity of the threatened wild rice Oryza rufipogon in both protected and unprotected populations in China between 2001 and 2020. Unprotected populations tended to have decreased census population sizes ( Nc ) compared to protected populations, although they both showed a reduction in effective population size ( Ne ). While allele diversity and expected heterozygosity remained stable, several populations, especially those without protection, exhibited a significant decrease in observed heterozygosity ( Ho ) and an increase in inbreeding ( F IS ). The level of genetic differentiation between populations did not change over time, but the number of private alleles increased and Ne varied in several populations, indicating the effects of genetic drift. Indicators for temporal trends in Ho , F IS , and Ne revealed that both protected and unprotected populations are facing warnings of declining genetic diversity, although some protected populations remain resilient, reflecting the genetic lag behind Nc change. Overall, these findings highlight the effectiveness of in situ conservation efforts in maintaining population size and genetic diversity, yet we also show the necessity of lasting population dynamics monitoring, using different genetic indicators.

Full realization of the RIBLL2 separator at the HIRFL-CSR facility - Xiao-Dong Xu; Yong Zheng; Zhi-Yu Sun; Yu-Nan Song; Bao-Hua Sun; Satoru Terashima; Chang-Jian Wang; Ge Guo; Guang-Shuai Li; Xiu-Lin Wei; Jun-Yao Xu; Ji-Chao Zhang; et al. (Science Bulletin, 2025)

Synergetic “amine scissors” break down cured epoxy resins with nearly 100% degradation efficiency - Furong Xie; Rong Chen; Chao Deng; Xiaoxin Li; Huiyan Yang; Yu Xie; Song Wang; Guo-Ming Weng (Chemical Engineering Journal, 2025)

Multi-Omics Exploration of Obesity Biomarkers in Sedentary and Weight Loss Cohorts - Hui Wang; Yixiao Zhuang; Rong Hua; Ting Yao; Kaiqing Lin; Yitao Zhang; Rui Huang; Ruwen Wang; Shanshan Guo; Qiwei Shen; Yikai Shao; Wei Wu; et al. (Phenomics, 2025)

Design, synthesis, biological evaluation, and in silico studies of imidazo[2,1-b][1,3,4]thiadiazole derivatives as cholinesterase inhibitors - Wen-Rong Du; Yi-Xuan Wang; Xue-Wei Zhou; Yong Lan; Ben-Ben Wei; Xin-Yuan Guo; Xiao-Ke Wang; Zheng-Yue Ma (Medicinal Chemistry Research, 2025)

Legume intercropping improves soil organic carbon stability in drylands: A 7-year experimental validation - Wei Wang; Meng-Ying Li; Yang Wang; Jian-Ming Li; Wei Zhang; Qin-Hui Wen; Shuang-Jin Huang; Guang-Rong Chen; Shuang-Guo Zhu; Jing Wang; Fazal Ullah; You-Cai Xiong (Agriculture, Ecosystems & Environment, 2025)

Integrative deep learning framework predicts lipidomics-based investigation of preservatives on meat nutritional biomarkers and metabolic pathways - Wei Jia; Aiai Guo; Wenwen Bian; Rong Zhang; Xin Wang; Lin Shi (Critical Reviews in Food Science and Nutrition, 2025)

Recombinant probiotic Escherichia coli delivers the polymeric protein of swine influenza virus for protection - Jin-Mei Sun; Wen-Qiang Zhang; Yan-Jin Li; Tian-Kui Guo; Rong-Rong Zhang; Yong-Lei Yang; Ying Zhao; Ling-Jiao Yu; Chun-Wei Shi; Gui-Lian Yang; Hai-Bin Huang; Yan-Long Jiang; et al. (Veterinary Microbiology, 2025)

Electrochemical behavior and the mechanism of nickel ion removal during zinc sulfate electrolysis via ultrasonic purification - Jianqiang Ye; Shixing Wang; Rong Zhu; Likang Fu; Jian Liu; Genwei Zhang; Guo Lin (Journal of Water Process Engineering, 2025)

Nonradicals-dominated peroxymonosulfate activation of g-C3N4/CeO2 floating beads for enhanced inactivation of M. aeruginosa: Performance studies and mechanistic insights - Dandan Wang; Jing Li; Rong Zhang; Beiyu Xin; Xueru Huang; Yang Wang; Jifeng Guo (Chemical Engineering Journal, 2025)

Comammox and ammonia-oxidizing archaea dominated the nitrification under different nitrogen fertilizer levels in acid purple soil of Southwest China - Jun Xie; Jianguo Jiang; Jie Lu; Wencai Dai; Huarong Guo; Yuanxue Chen; Rong Huang; Zifang Wang; Ming Gao (Applied Soil Ecology, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Recent advances in cold plasma technology for enhancing the safety and quality of meat and meat products: A comprehensive review - Changyan Zhang; Yulong Luo; Ziyao Deng; Rui Du; Mei Han; Junqin Wu; Wenxiu Zhao; Rong Guo; Yanru Hou; Songlei Wang (Food Research International, 2025)

Inhibition of electron transfer in anaerobic ammonia-oxidized granular sludge by polyethylene terephthalate microplastics and nanoplastics: A new perspective on molecular docking and molecular dynamics simulations - Chaofan Xie; Dongyue Li; Jiarui Li; Linzhu Du; Yanshuo Wu; Rong Luo; Zheng Wang; Jun Li; Yuhan Zhu; Wei Guo (Chemical Engineering Journal, 2025)

Precipitation addition during growing and non-growing seasons interactively affects the abundance of soil nematode communities in a semi-arid steppe - Yaning Li; Jingwei Guo; Xun Wang; Taohui Lian; Rong Yuan; Jiarui Feng; Cancan Zhao; Renhui Miao; Yinzhan Liu (CATENA, 2025)

Chitooligosaccharide application enhanced the growth and phytoremediation efficiency of industrial hemp in Cd-contaminated soils - Xinlin Zhao; Yuanchang Wang; Chenyuan Wang; Wei Zhou; Da Ouyang; Shuaishuai Gao; Xiaofei Tan; Rong Huang; Yuan Guo (Bioresource Technology, 2025)

An auto-configurable and interpretable ensemble learning framework for optimal catalyst design of green methanol production via Bayesian optimization - Dongwen Rong; Zhao Wang; Qiwen Guo; Runjie Bao; Qingchun Yang (Journal of Cleaner Production, 2025)

Investigating the matrix effect of high/low methoxyl pectins on typical aroma of apple juice using HS-SPME-GC–MS and NMR analysis - Wan Qing Li; Hui Liu; Yu Rong Guo; Xiao Yu Wang; Peng Tao Zhao (Food Chemistry, 2025)

A novel measurement for evaluating the capture efficiency of local ventilation system using background oriented schlieren - Junhao Rong; Yanqiu Huang; Yihang Zhao; Yi Wang; Xin Li; Junwei Guo; Wenyang Wang; Shengnan Guo (Building and Environment, 2025)

Path planning of greenhouse electric crawler tractor based on the improved A* and DWA algorithms - Huiping Guo; Yi Li; Hao Wang; Chensi Wang; Jiao Zhang; Tingwei Wang; Linrui Rong; Haoyu Wang; Zihao Wang; Yaobin Huo; Shaomeng Guo; Fuzeng Yang (Computers and Electronics in Agriculture, 2024)

Effects of material and structure types on drifting speed of fish aggregation devices (FADs) in tuna purse seine fishery - Yucheng Wang; Cheng Zhou; Rong Wan; Liuxiong Xu; Shaojian Guo (Marine Pollution Bulletin, 2024)

Off-site production of plasma-activated water for efficient disinfection: The crucial role of high valence NOx and new chemical pathways - Zifeng Wang; Xiangyu Wang; Shenghang Xu; Renwu Zhou; Mingyan Zhang; Wanchun Li; Zizhu Zhang; Luge Wang; Jinkun Chen; Jishen Zhang; Li Guo; Dandan Pei; et al. (Water Research, 2024)

Investigation of the effects of polyethylene microplastics at environmentally relevant concentrations on the plant-soil-microbiota system: A two-year field trial - Meiling Xu; Wenqian Ma; Yu Yao; Qiao Xu; Wenchao Du; Ying Yin; Rong Ji; Xiaozhi Wang; Hongyan Guo (Science of The Total Environment, 2024)

Secondary activation on plasma-activated water by plasma-treated cotton for restoring and enhancing disinfection effect - Zifeng Wang; Shenghang Xu; Xiangyu Wang; Dingxin Liu; Wanchun Li; Rusen Zhou; Qiuyi Yue; Pengfei Zhang; Jishen Zhang; Hao Zhang; Li Guo; Dandan Pei; et al. (Journal of Hazardous Materials, 2024)

Microscopic mechanisms and durability evaluation under freeze-thaw conditions of heavy metal solidification in red mud-slag geopolymer - Lu Zhou; Xin Xu; Qing Wang; Junboum Park; Yongming Han; Lisheng Guo; Rong Chen (Journal of Environmental Chemical Engineering, 2024)

Origin of the Narenwula quartz vein-type W deposit, Inner Mongolia, China: Insights from geochemistry of hosting granites, fluid inclusions, H-O-S isotopes, and wolframite trace elements - Lin-Wei Wang; De-Hui Zhang; Jia-Jun Liu; Zhu Li; Rong-Zhen Zhang; Xi Diao; Bin Zhang; Guo-Ming Weng (Journal of Asian Earth Sciences, 2024)

Immunoprotective effect of recombinant Lactobacillus plantarum expressing largemouth bass virus MCP on largemouth bass - Yong-Lei Yang; Rong-Rong Zhang; Jing-Yi Pang; Jun-Hong Xing; Tian-Kui Guo; Chun-Wei Shi; Gui-Lian Yang; Hai-Bin Huang; Yan-Long Jiang; Jian-Zhong Wang; Xin Cao; Nan Wang; et al. (Fish & Shellfish Immunology, 2024)

p-Smad3 differentially regulates the cytological behavior of osteoclasts before and after osteoblasts maturation - Jiapeng Ye; Zhen Hua; Jirimutu Xiao; Yang Shao; Shaoshuo Li; Heng Yin; Mao Wu; Yi Rong; Bowen Hong; Yang Guo; Yong Ma; Jianwei Wang (Molecular Biology Reports, 2024)

Neutralizing chimeric heavy-chain antibody targeting the L-HN domain of Clostridium botulinum neurotoxin type F - Kaiyue Sun; Shudi Luo; Yujia Jiang; Jiazheng Guo; Xi Wang; Kexuan Cheng; Changyan Xu; Yixiao Zhang; Chen Gao; Jiansheng Lu; Peng Du; Yunzhou Yu; et al. (Archives of Toxicology, 2024)

FGTN: Fragment-based graph transformer network for predicting reproductive toxicity - Jia-Nan Ren; Qiang Chen; Hong-Yu-Xiang Ye; Cheng Cao; Ya-Min Guo; Jin-Rong Yang; Hao Wang; Muhammad Zafar Irshad Khan; Jian-Zhong Chen (Archives of Toxicology, 2024)

The different impacts of functional network centrality and connectivity on the complexity of brain signals in healthy control and first-episode drug-naïve patients with major depressive disorder - Shanling Ji; Wei An; Jing Zhang; Cong Zhou; Chao-Gan Yan; Xiao Chen; Li-Ping Cao; Wei Chen; Yu-Qi Cheng; Yi-Ru Fang; Qi-Yong Gong; Wen-Bin Guo; et al. (Brain Imaging and Behavior, 2024)

Performance of a novel annular electric field membrane bioreactor and its membrane fouling control in treating catering wastewater - Rong Zhang; Mengqian Li; Huan Ma; Yanyan Wang; Beiyu Xin; Jifeng Guo (Chemosphere, 2024)

Study on Translational toxicology of Senna obtusifolia aqueous extract - Xin Guo; Liping Gong; Chong Guo; Taotao Cai; Nana Huang; Xianhui Shen; Lisong Sheng; Rongrong Li; Yanqing Wang; Xinmei Zhao; Wenhe Guo; Rong Sun (Toxicon, 2024)

Emission, distribution and formation characteristics of polybrominated dibenzo-p-dioxins and dibenzofurans during co-disposal of hexabromocyclododecane-containing waste in cement kiln - Jian Wang; Bingcheng Lin; Xiao Wang; Guorui Liu; Rong Jin; Jukun Xiong; Jianping Guo; Yinming Li; Minghui Zheng (Science of The Total Environment, 2024)

PM2.5 constituents associated with mortality and kidney failure in childhood-onset lupus nephritis: A 19-year cohort study - Guohua He; Yaqi Wang; Cheng Cheng; Jianhui Guo; Zhilang Lin; Ziyun Liang; Bei Jin; Liyuan Tao; Liping Rong; Lizhi Chen; Tianxin Lin; Yining Hua; et al. (Science of The Total Environment, 2024)

Evaluating the hydrodynamic characteristics and shape configuration of fine-mesh nettings for sampling nets - Zhiqiang Liu; Fuxiang Hu; Rong Wan; Tongzheng Zhang; Yucheng Wang; Shaojian Guo; Cheng Zhou (Ocean Engineering, 2024)

Gene expression profiles and metabolic pathways responsible for male sterility in cybrid pummelo - Rong Wang; Yang-Cao Shi; Bo Zhang; Wan-Rong Liu; Feng-Quan Tan; Fang Lu; Nan Jiang; Lai-Chao Cheng; Kai-Dong Xie; Xiao-Meng Wu; Wen-Wu Guo (Plant Cell Reports, 2024)

Effects of microplastics on potato verticillium wilt and microbial community of rhizosphere soil - Naqi Cui; Hongwu Liang; Weisong Zhao; Mingzhu Zhao; Yu Wang; Qinggang Guo; Zihui Rong; Shezeng Li; Ping Ma (Applied Soil Ecology, 2024)

Precipitation contributes to alleviating pollution of rubber-derived chemicals in receiving watersheds: Combining confluent stormwater runoff from different functional areas - Yue-Hong Liu; Yu-Xian Mei; Jing-Yi Wang; Shan-Shan Chen; Jia-Li Chen; Nan Li; Wang-Rong Liu; Jian-Liang Zhao; Qian-Qian Zhang; Guang-Guo Ying (Water Research, 2024)

Late cretaceous intraplate magmatism in Central and South Pamir: Response to edge-driven convection - Xin Ma; Jian Wang; Wei Dan; Qiang Wang; Guo-Rong Tang; Mustafo Gadoev; Ilhomjon Oimahmadov; Murodov Azamdzhon; Sharifjon Odinaev; Gong-Jian Tang (Lithos, 2024)

Combating coal-burning-borne endemic arsenism in Shaanxi Province, Northwest China: The impact of high-arsenic coal ban, improved cook-stoves, and health education - Yujie Ning; Chaowei Wang; Shujin Li; Sijie Chen; Feiyu Zhang; Rong Zhou; Yuequan Yuan; Xi Lv; Yifan Wu; Yu Zhang; Zhongxue Fan; Xiaoqian Li; et al. (Journal of Hazardous Materials, 2024)

Construction of oxygen-doped g-C3N4/BiOCl (S-scheme) heterojunction: Efficient degradation of tetracycline in wastewater - Yuan Wei; Yu-Bing Liu; Chao Liu; Xin Li; Guang-Hong Zhao; Rong-Hui Liu; Hong-Yu Wang; Yan-Yan Jiang; Yu-Lan Zhang; Yu-Hui Gao; Gao-Feng Shi; Guo-Ying Wang (Journal of Environmental Chemical Engineering, 2024)

Investigation on formation and combustion process of carbon deposits from coke oven riser during waste heat recovery - Yaqiang Yuan; Tao Rong; Huafang Yu; Hao Guo; Yan Gao; Jingsong Wang; Qingguo Xue; Haibin Zuo (Fuel, 2024)

Gum arabic coating alleviates chilling injury of cold-stored peach by regulating reactive oxygen species, phenolic, and sugar metabolism - Zengyu Gan; Yupei Zhang; Ziteng Jin; Yongjie Wang; Jiali Li; Caining Yang; Qing Cao; Jinyin Chen; Zhenbang Rong; Xuming Lu; Suqin Guo (Food Chemistry, 2024)

Enhanced solar-driven steam generation and water purification using 3D arch solar evaporators - Yong-Gang Wu; Chao-Hua Xue; Xiao-Jing Guo; Meng-Chen Huang; Hui-Di Wang; Chao-Qun Ma; Li Wan; Shi-Qiang Lv; Wen-Min Zhang; Rong-Rong Gao (Desalination, 2024)

Design, synthesis and evaluation of imidazo[1,2-a]pyrazin-8(7H)-one derivatives as acetylcholinesterase inhibitors and antioxidants - Wen-Rong Du; Ben-Ben Wei; Xin-Yuan Guo; Yong Lan; Pan-Pan Shang; Yi-Xuan Wang; Xue-Wei Zhou; Xiao-Ke Wang; Zheng-Yue Ma (Medicinal Chemistry Research, 2024)

Label-Free Detection of Programmed Death-Ligand 1 for Prognosis Using a Truncated Aptamer and SYBR Green I - Ling Li; Zheng-Ling Li; Wei Wang; Xin-Xin Long; Ping Liu; Guo-Tian Wang; Shi-Qing Sun; Rong-Lian Du (Journal of Fluorescence, 2024)

Metabolic Heterogeneity and Potential Immunotherapeutic Responses Revealed by Single-Cell Transcriptomics of Breast Cancer - Shicong Tang; Qing Wang; Ke Sun; Ying Song; Rui Liu; Xin Tan; Huimeng Li; Yafeng Lv; Fuying Yang; Jiawen Zhao; Sijia Li; Pingping Bi; et al. (Apoptosis, 2024)

BaP/BPDE exposure causes human trophoblast cell dysfunctions and induces miscarriage by up-regulating lnc-HZ06-regulated IL1B - Jiarong Guo; Jingsong Zhao; Peng Tian; Zhongyan Xu; Rong Wang; Weina Chen; Xiaoqing Wang; Shukun Wan; Yang Yang; Huidong Zhang (Journal of Hazardous Materials, 2024)

Application of coalbed methane assisted iron ore sintering: Injection effect, pollutant abatement and economic evaluation - Yaqiang Yuan; Tao Rong; Huafang Yu; Haibin Zuo; Hao Guo; Yan Gao; Jingsong Wang; Qingguo Xue (Journal of Cleaner Production, 2024)

Corrigendum to “Distribution of organophosphorus pesticides and its potential connection with probiotics in sediments of a shallow freshwater lake” [Journal of Contaminant Hydrology 261 (2024) 104306] - Yanping Hu; Rong Xiao; Yaping Wang; Junming Li; Congling Guo; Ling Zhang; Kegang Zhang; Milko A. Jorquera; Javiera Manquian; Wenbin Pan (Journal of Contaminant Hydrology, 2024)

Accumulation and ecological risk assessment of diazinon in surface sediments of Baiyangdian lake and its potential impact on probiotics and pathogens - Yaping Wang; Rong Xiao; Yanping Hu; Junming Li; Congling Guo; Ling Zhang; Kegang Zhang; Milko A. Jorquera; Wenbin Pan (Environmental Pollution, 2024)

Scalable thermochromic superhydrophobic collagen fiber-based wearable materials for all-weather self-adaptive radiative cooling and solar heating - Meng-Chen Huang; Chao-Hua Xue; Zhongxue Bai; Hui-Di Wang; Chao-Qun Ma; Yong-Gang Wu; Li Wan; Long Xie; Shi-Qiang Lv; Rong-Rong Gao; Wen-Min Zhang; Jun Cheng; et al. (Chemical Engineering Journal, 2024)

Arc building and maturation of the Lombok Island, East Sunda Arc - Guo-Rong Tang; Wei Dan; Adi Maulana; Jian Wang; Xiu-Zheng Zhang; Yun-Ying Zhang; Xin Ma; Qiang Wang; Xi-Jun Liu; Gong-Jian Tang (Chemical Geology, 2024)

Argon non-thermal plasma treatment promotes the development of rice (Oryza sativa L.) in saline alkali environments - Kai Liu; Yan-Jiang Feng; Jun-Xiang Guo; Gui-Ling Wang; Li-Li Shan; Shi-Wei Gao; Qing Liu; Hu-Nan Sun; Xi-Yu Li; Xing-Rong Sun; Jing-Yang Bian; Taeho Kwon (Protoplasma, 2024)

Assessment of the hormesis effect and toxic damage of short-term low-dose aflatoxin B1 in grass carp (Ctenopharyngodon idellus) - Jin-long Li; Jia-rong Guo; Pei Wang; Jun-zhi Zhang; Zhi-gang He; Jin-long Wang; Yi Hu (Frontiers in Marine Science, 2024)
The present study was conducted to evaluate the hormesis and toxicity of short-term low-dose aflatoxin B1 in grass carp ( Ctenopharyngodon idellus ). Triplicate isonitrogenous and isocaloric aflatoxin B1 diets—CD (control, 0 ug/kg), D1 (20 ug/kg), and D2 (500 ug/kg)—were prepared and fed to grass carp with an initial mean body weight of (15.2 ± 0.1) g for 56 days. The results showed that the weight gain rate and specific growth rate of grass carp fed diet D2 were significantly higher, and the feed coefficient and crude fat content of the whole body were significantly lower ( P < 0.05) compared with those fed diet CD. Serum superoxide dismutase content of grass carp fed D1 diet increased significantly ( P < 0.05) with an increasing dose of aflatoxin B1, but when the dose reached 500 ug/kg (D2), serum superoxide dismutase, complement C3, and immunoglobulin M of grass carp decreased significantly ( P < 0.05), while malondialdehyde increased significantly ( P < 0.05). After short-term feeding of aflatoxin B1-containing diets (D1 and D2), liver body index, visceral body index, serum total cholesterol, triglyceride, and urea nitrogen content of grass carp increased significantly ( P < 0.05), total bile acid secretion decreased significantly ( P < 0.05), and structural damages such as increase in vacuoles, organizational structure loosening, and nucleus translocation were observed in the liver. Meanwhile, liver function indexes such as serum alanine aminotransferase, aspartate aminotransferase, and alkaline phosphatase increased significantly with the increase of aflatoxin B1 dose ( P < 0.05). In addition, the height of intestinal villi, crypt depth, villus–crypt ratio, and tubular cell number, as well as the content of trypsin and lipase activities in the intestine of grass carp in the D2 group, were significantly higher than those in the CD group ( P < 0.05). In conclusion, after a short-term intake of low doses of aflatoxin B1 (≤500 ug/kg), the toxicological damage of aflatoxin B1 was pronounced, although it produced a certain degree of hormesis on the growth performance and intestinal structure and function of grass carp. At a dose of 20 ug/kg, the non-specific immune system and liver structure and function of grass carp showed obvious toxic damage.

Corrigendum to “Pathogen profile of Baiyangdian Lake sediments using metagenomic analysis and their correlation with environmental factors” [Sci. Total Environ. 913 (2024) 169628] - Rong Xiao; Yanping Hu; Yaping Wang; Junming Li; Congling Guo; Ling Zhang; Kegang Zhang; Milko A. Jorquera; Jacquelinne J. Acuña; Wenbin Pan (Science of The Total Environment, 2024)

Seasonal dynamics of the microbiota and nutritional composition in bee bread from Apis cerana and Apis mellifera colonies - Jia-Li Li; Wan-Li Li; Jun Zhang; Yan-tao Pang; Jian Xiong; Ping Wu; Bang-rong Wei; Xi-Jie Li; Qi Huang; Qi-He Tang; Chong-Hui Zhao; Qian Wang; et al. (Food Research International, 2024)

Collective effects of rising average temperatures and heat events on oviparous embryos - Liang Ma; Dan‐Yang Wu; Yang Wang; Joshua M. Hall; Chun‐Rong Mi; Hong‐Xin Xie; Wei‐Jie Tao; Chao Hou; Kun‐Ming Cheng; Yong‐Pu Zhang; Ji‐Chao Wang; Hong‐Liang Lu; et al. (Conservation Biology, 2024)
Survival of the immobile embryo in response to rising temperature is important to determine a species’ vulnerability to climate change. However, the collective effects of 2 key thermal characteristics associated with climate change (i.e., rising average temperature and acute heat events) on embryonic survival remain largely unexplored. We used empirical measurements and niche modeling to investigate how chronic and acute heat stress independently and collectively influence the embryonic survival of lizards across latitudes. We collected and bred lizards from 5 latitudes and incubated their eggs across a range of temperatures to quantify population‐specific responses to chronic and acute heat stress. Using an embryonic development model parameterized with measured embryonic heat tolerances, we further identified a collective impact of embryonic chronic and acute heat tolerances on embryonic survival. We also incorporated embryonic chronic and acute heat tolerance in hybrid species distribution models to determine species’ range shifts under climate change. Embryos’ tolerance of chronic heat (T‐chronic) remained consistent across latitudes, whereas their tolerance of acute heat (T‐acute) was higher at high latitudes than at low latitudes. Tolerance of acute heat exerted a more pronounced influence than tolerance of chronic heat. In species distribution models, climate change led to the most significant habitat loss for each population and species in its low‐latitude distribution. Consequently, habitat for populations across all latitudes will shift toward high latitudes. Our study also highlights the importance of considering embryonic survival under chronic and acute heat stresses to predict species’ vulnerability to climate change.

Analysis of parameters for spray-local exhaust ventilation (SLEV) to minimize high-temperature smoke pollutants and reduce energy consumption - Shengnan Guo; Yanqiu Huang; Yi Wang; Zhenpeng Wang; Yirui Zhang; Zhubin Wang; Junhao Rong (Sustainable Cities and Society, 2024)

SAD2 functions in plant pathogen Pseudomonas syringae pv tomato DC3000 defense by regulating the nuclear accumulation of MYB30 in Arabidopsis thaliana - Tiantian Shi; Yuan Zheng; Rui Wang; Sha Li; Andi Xu; Luoying Chen; Yuanhang Liu; Rong Luo; Chenchen Huang; Yinglu Sun; Jinfeng Zhao; Xiaoying Guo; et al. (Plant Science, 2024)

Phyllanthus emblica Linn: A comprehensive review of botany, traditional uses, phytonutrients, health benefits, quality markers, and applications - Qin-Ge Ma; Lei Wang; Rong-Hua Liu; Jin-Bin Yuan; Hui Xiao; Zhang-Yang Shen; Jia-Xin Li; Jia-Zeng Guo; Lan Cao; Hui-Lian Huang; Rong-Rui Wei (Food Chemistry, 2024)

Surface PD-1 expression in T cells is suppressed by HNRNPK through an exonic splicing silencer on exon 3 - Jiayun Wang; Lingyan Yan; Xu Wang; Rong Jia; Jihua Guo (Inflammation Research, 2024)

Intestinal microbiota via NLRP3 inflammasome dependent neuronal pyroptosis mediates anxiety-like behaviour in mice exposed to 3.5 GHz radiofrequency radiation - Gui-qiang Zhou; Xing Wang; Peng Gao; Tong-zhou Qin; Ling Guo; Zhao-wen Zhang; Zhi-fei Huang; Jia-jin Lin; Yun-tao Jing; Hao-nan Wang; Chun-ping Wang; Gui-rong Ding (Science of The Total Environment, 2024)

OsPRMT6a-mediated arginine methylation of OsJAZ1 regulates jasmonate signaling and spikelet development in rice - Kun Dong; Fuqing Wu; Siqi Cheng; Shuai Li; Feng Zhang; Xinxin Xing; Xin Jin; Sheng Luo; Miao Feng; Rong Miao; Yanqi Chang; Shuang Zhang; et al. (Molecular Plant, 2024)

Inactivation of microorganisms on fabrics using plasma-activated nebulized mist driven by different plasma gases - Pengyu Zhao; Sihong Ma; Li Guo; Yikang Jia; Rui Zhang; Min Chen; Zifeng Wang; Dingxin Liu; Yuan Zhao; Xiaohua Wang; Mingzhe Rong (Journal of Hazardous Materials, 2024)

Quantifying the teleconnections of carbon storage in construction land and its socioeconomic driving forces in Guangdong Province - Rong Wu; Shijie Zhou; Hongxu Guo; Shaojian Wang (Journal of Cleaner Production, 2024)

ZnO nanorod coatings attenuate antibiotic resistance genes (ARGs) on their surface biofilms in estuarine environment - Xing-pan Guo; Rong-rong Sha; Yu-cen Wang; Jia Yan; Bo Peng; Zuo-shun Niu; Wen-liang Liu; Xin Li; Yi Yang (Journal of Environmental Chemical Engineering, 2024)

Acid induced dispersive liquid–liquid microextraction based on in situ formation of hydrophobic deep eutectic solvents for the extraction of bisphenol A and alkylphenols in water and beverage samples - Kaige Zhang; Jing Wang; Rong Guo; Qiujun Nie; Guifen Zhu (Food Chemistry, 2024)

Boosting persulfate activation through efficient π → π* transition activated by Cu ion anchored porphyrin-based metal–organic framework - Wen-Qiang Li; Oleksandr Savateev; Yuan-Ming Li; Jian-Kang Zheng; Yi-Xuan Wang; Nannan Hou; Xiao-Cheng Liu; Rong-Rong Ding; Xiao-Guo Zhou; Yang Wang; Xian-Yang Shi; Yang Mu (Chemical Engineering Journal, 2024)

Enhanced anaerobic digestion performance and sludge filterability by membrane microaeration for anaerobic membrane bioreactor application - Chun-Hai Wei; Zheng-Wei Wang; Jian-Hua Dai; Kang Xiao; Hua-Rong Yu; Fang-Shu Qu; Hong-Wei Rong; Jun-Guo He; Huu Hao Ngo (Bioresource Technology, 2024)

Chemical constituents from Albatrellus confluence and their chemotaxonomic significance - Qing-Fang Wang; Jing-Rong Ou-Yang; Ting-Ting Guo; Ming-Ming Li; Hong-Ping He (Biochemical Systematics and Ecology, 2024)

Genome-wide analysis of in vivo-evolved Candida auris reveals multidrug-resistance mechanisms - Xin-Fei Chen; Han Zhang; Ling-Li Liu; Li-Na Guo; Wen-Jing Liu; Ya-Li Liu; Ding-Ding Li; Ying Zhao; Ren-Yuan Zhu; Yi Li; Rong-Chen Dai; Shu-Ying Yu; et al. (Mycopathologia, 2024)

Study on spray characteristics of micro-nano bubble premixed fuel - Rong Xuan; Liang Guo; Ningning Cai; Wanchen Sun; Yuying Yan; Hao Zhang; Yanling Chen; Han Wang; Junfeng Zhang; Youxin Ge (Fuel, 2024)

Terpenes based hydrophobic deep eutectic solvents for dispersive liquid-liquid microextraction of aliphatic aldehydes in drinking water and alcoholic beverages - Kaige Zhang; Rong Guo; Yunhe Wang; Jing Wang; Qiujun Nie; Guifen Zhu (Chemosphere, 2024)

Optimization of alkaline hydrothermal treatment for humic acids production from corn straw digestate using the response surface methodology - Shuai-Ze Han; Bo-Tao Zhang; Man-Qian Wang; Rong-Bo Guo; Shan-Fei Fu (Journal of Environmental Chemical Engineering, 2024)

Seed germination and seedling growth response of Leymus chinensis to the allelopathic influence of grassland plants - Kaili Wang; Pengpeng Dou; Zhengzhou Miao; Jing Huang; Qian Gao; Lizhu Guo; Kesi Liu; Yuping Rong; Ding Huang; Kun Wang (Oecologia, 2024)

Cypermethrin induces Sertoli cell apoptosis through endoplasmic reticulum-mitochondrial coupling involving IP3R1-GRP75-VDAC1 - Rui Zhang; Xu-Xu Wang; Jia-fei Xie; Ting-ting Yao; Qian-wen Guo; Qi Wang; Zhen Ding; Jin-Peng Zhang; Mei-Rong Zhang; Li-Chun Xu (Reproductive Toxicology, 2024)

Hydrodynamic characteristics of frustum-type depressor for sampling midwater trawl - Zhiqiang Liu; Fuxiang Hu; Rong Wan; Yucheng Wang; Shaojian Guo; Hao Yan; Cheng Zhou (Ocean Engineering, 2024)

Flexible and binder free electrode with d-p band center manipulated MoTe2 nanosheets towards high energy Lithium–Sulfur batteries - Meng Guo; Shaonan Gu; Rong Zhou; Zheng Zhang; Shuzheng Xu; Yinan Wang; Guowei Zhou (Chemical Engineering Journal, 2024)

Anemoside B4, a new pyruvate carboxylase inhibitor, alleviates colitis by reprogramming macrophage function - Qing-hua Liang; Qiu-rong Li; Zhong Chen; Li-juan Lv; Yu Lin; Hong-lv Jiang; Ke-xin Wang; Ming-yue Xiao; Nai-xin Kang; Peng-fei Tu; Shi-liang Ji; Ke-jun Deng; et al. (Inflammation Research, 2024)

Epidural administration of large dose of opioid μ receptor agonist may impair cardiac functions and myocardial viability via desensitizing transient receptor potential vanilloid 1 - Xiang Ma; Zheng Guo; Mu-Rong Li; Lu Chen; Xing Zhao; Tian-Qi Wang; Tao Sun (Toxicology and Applied Pharmacology, 2024)

Pathogen profile of Baiyangdian Lake sediments using metagenomic analysis and their correlation with environmental factors - Rong Xiao; Yanping Hu; Yaping Wang; Junming Li; Congling Guo; Junhong Bai; Ling Zhang; Kegang Zhang; Milko A. Jorquera; Jacquelinne J. Acuña; Wenbin Pan (Science of The Total Environment, 2024)

Numerical simulation-based hydrodynamic interaction of bottom-set gillnet with current and ecological implications - Shaojian Guo; Cheng Zhou; Rong Wan; Jie Cao; Yucheng Wang (Ocean Engineering, 2024)

Distribution of organophosphorus pesticides and its potential connection with probiotics in sediments of a shallow freshwater lake - Yanping Hu; Rong Xiao; Yaping Wang; Junming Li; Congling Guo; Junhong Bai; Ling Zhang; Kegang Zhang; Milko A. Jorquera; Javiera Manquian; Wenbin Pan (Journal of Contaminant Hydrology, 2024)

Experiment and dynamic simulation of hydrogen recovery from hydrogen-containing gas mixtures via hydrate-membrane coupling method - Jingbo Gao; Qiang Sun; Jia Luo; Leyan Li; Ninghui Liu; Rong Ma; Hang Zhao; Xiangming Li; Zongyu Qin; Yiwei Wang; Xuqiang Guo (Fuel, 2024)

Thermal extraction of coal and derivatives to prepare hot-pressed coal briquette for COREX application - Yuanhao Yu; Haibin Zuo; Yajie Wang; Hongyi Kang; Hao Guo; Tao Rong; Jingxiu Wang (Fuel, 2024)

Molecular dynamics simulation and experimental analysis of nucleation and growth mechanism of mixed inorganic salts in supercritical water - Siqi Rong; Ruoyu Wang; Anlan Xie; Zhiyong Peng; Peng Cao; Mingyi Zhang; Jinhua Cui; Yunan Chen; Liejin Guo (Chemical Engineering Journal, 2024)

Cascaded antibody directionality relying on a zinc-based nanocomposite for performance enhancement of multiplex lateral flow immunoassay - Xuechi Yin; Ziai Deng; Leina Dou; Jing Guo; Chengyuan Yang; Zhuo Dai; Rong Wang; Yanru Wang; Jianlong Wang; Daohong Zhang (Chemical Engineering Journal, 2024)

Toxicity of common biocides used in aquaculture to embryos and larvae of Brachymystax tsinlingensis Li - Xing‐chen Guo; Zhi‐peng Chu; Rong‐qun Song; Zhen‐lu Wang; Rui‐jiao Li; Dong‐mei Xiong; Mu‐zi Zhang; Hai‐bo Jiang; Jian Shao (Journal of Fish Biology, 2024)
Brachymystax tsinlingensis Li is a threatened fish species endemic to China. With the problems of environmental factors and seeding breeding diseases, it is important to further improve the efficiency of seeding breeding and the basis of resource protection. This study investigated the acute toxicity of copper, zinc and methylene blue (MB) on hatching, survival, morphology, heart rate (HR) and stress behaviour of B. tsinlingensis . Eggs (diameter: 3.86 ± 0.07 mm, weight: 0.032 ± 0.004 g) of B. tsinlingensis were selected randomly from artificial propagation and developed from eye‐pigmentation‐stage embryos to yolk‐sac stage larvae (length: 12.40 ± 0.02 mm, weight: 0.03 ± 0.001 g) and exposed to different concentrations of Cu, Zn and MB for 144 h in a series of semi‐static toxicity tests. The acute toxicity tests indicated that the 96‐h median lethal concentration (LC 50 ) values of the embryos and larvae were 1.71 and 0.22 mg l −1 for copper and 2.57 and 2.72 mg l −1 for zinc, respectively, whereas the MB LC 50 after 144‐h exposure for embryos and larvae were 67.88 and 17.81 mg l −1 , respectively. The safe concentrations of copper, zinc and MB were 0.17, 0.77 and 6.79 mg l −1 for embryos and 0.03, 0.03 and 1.78 mg l −1 for larvae, respectively. Copper, zinc and MB treatments with concentrations greater than 1.60, 2.00 and 60.00 mg l −1 , respectively, led to a significantly low hatching rate and significantly high embryo mortality ( P −1 led to significantly high larvae mortality ( P P P B. tsinlingensis embryos or larvae might be more resistant to copper, zinc and MB than other members of the Salmonidae family, which benefits their resource protection and restoration.

Disclosing phototransformation mechanisms of decabromodiphenyl ether (BDE-209) in different media by simulated sunlight: Implication by compound-specific stable isotope analysis - Guoguang Wang; Chuanyuan Li; Shuaihao Liu; Ziao Xing; Pengxu Guo; Zixuan Hao; Maojiao Li; Haixia Wang; Guangzhi Rong; Yu Liu (Environmental Science and Pollution Research, 2024)

Two birds with one stone: A magneto-optical dual-stimuli-responsive intelligent Pickering emulsion for efficient conversion of glucose to 5-hydroxymethylfurfural - Zhong-Qiu Liu; Jia-Liang Guo; Rong-Hua Liang; Feng-Xiang Wang; Zhan-Ku Li; Yujing Liu; Anguo Ying (Chemical Engineering Journal, 2024)

Voluntary running wheel exercise induces cognitive improvement post traumatic brain injury in mouse model through redressing aberrant excitation regulated by voltage-gated sodium channels 1.1, 1.3, and 1.6 - Dan Wang; Hui-Xiang Zhang; Guo-Ji Yan; Hao-Ran Zhao; Xiao-Han Dong; Ya-Xin Tan; Shan Li; Min-Nan Lu; Rong Mei; Li-Na Liu; Xu-Yang Wang; Yan-Bin Xiyang (Experimental Brain Research, 2024)
Traumatic brain injury (TBI) leads to disturbed brain discharge rhythm, elevated excitability, anxiety-like behaviors, and decreased learning and memory capabilities. Cognitive dysfunctions severely affect the quality of life and prognosis of TBI patients, requiring effective rehabilitation treatment. Evidence indicates that moderate exercise after brain injury decreases TBI-induced cognitive decline. However, the underlying mechanism remains unelucidated. Our results demonstrate that TBI causes cognitive impairment behavior abnormalities and overexpression of Nav1.1, Nav1.3 and Nav1.6 proteins inside the hippocampus of mice models. Three weeks of voluntary running wheel (RW) exercise treatments before or/and post-injury effectively redressed the aberrant changes caused by TBI. Additionally, a 10% exercise-conditioned medium helped recover cell viability, neuronal sodium current and expressions of Nav1.1, Nav1.3 and Nav1.6 proteins across cultured neurons after injury. Therefore, the results validate the neuroprotection induced by voluntary RW exercise treatment before or/and post-TBI. The RW exercise-induced improvement in cognitive behaviors and neuronal excitability could be associated with correcting the Nav1.1, Nav1.3, and Nav1.6 expression levels. The current study proves that voluntary exercise is an effective treatment strategy against TBI. The study also highlights novel potential targets for rehabilitating TBI, including the Navs proteins.

Evaluation of the ecohydrological separation of different geomorphological units in a semi-arid area - Yu Zhang; Mingjun Zhang; Yuquan Qiang; Jiaxin Wang; Rong Guo; Deye Qu; Shengjie Wang (Applied Geochemistry, 2024)

A near-infrared fluorescent probe for viscosity: Differentiating cancer cells from normal cells and dual-modal imaging in tumor mice - Jing-Jing Chao; Hui Zhang; Zhi-Qing Wang; Qiao-Rong Liu; Guo-Jiang Mao; Yongfei Li; Chun-Yan Li (Analytica Chimica Acta, 2024)

A study on the cyclic shear and particle breakage characteristics of the interface between steel and calcareous sand - Rui Wang; Jukun Guo; Shengyou Lei; Xiaowei Wang; Wentao Rong; Zhihua Yu (Marine Georesources & Geotechnology, 2023)

Screening of small molecule compounds targeting hnRNPA2 protein - Yuan-Rong Zheng; Chao-Jie Wang; Ling Yang; Yu-Jun Zhang; Mei-Juan Fang; He Chang; Kai-Qiang Guo; Song-Lin Shi (Medicinal Chemistry Research, 2023)

The expression of CD86 in CD3+CD56+ NKT cells is associated with the occurrence and prognosis of sepsis-associated encephalopathy in sepsis patients: a prospective observational cohort study - Sheng-long Chen; Xiao-yu Liu; Jun-hong Huang; Lu-hua Xian; Xu-sheng Li; Kang-rong Wang; Jing Li; Tian-cao Zhang; Guo-ge Huang; Xin-qiang Liu; Hong-ke Zeng; Mao-hua Zhou; et al. (Immunologic Research, 2023)

Determination and petroleum geochemical significance of short-chain alkylbenzenes in lacustrine source rocks - Zhao-Wen Zhan; Guo-Xiang Wang; Yankuan Tian; Xin Zhan; Tian Liang; Yao-Ping Wang; Yan-Rong Zou; Ping'an Peng (Organic Geochemistry, 2023)

Enhancing simultaneous desulfurization and denitrification efficiency of cement kiln exhaust gas via co-catalytic Fenton oxidation process - Tongsheng Zhang; Hui Peng; Rong Chen; Yiqun Guo; Jiawei Wang; Xinzhi Chen; Jiangxiong Wei; Qijun Yu (Journal of Cleaner Production, 2023)

Metabonomics analysis of microalga Scenedesmus obliquus under ciprofloxacin stress - Yue Wang; Weihao Ning; Shengnan Li; Changfei Gao; Rong Cui; Wanqian Guo; Jo-Shu Chang; Shih-Hsin Ho (Environmental Research, 2023)

Membrane fabrication and configuration design development of photothermal membrane distillation (PMD) - Guo-Rong Xu; Min Wang; Ke Xu; He-Li Zhao; Qian Liu (Desalination, 2023)

Failure Modes of Jointed Granite Subjected to Weak Dynamic Disturbance Under True-Triaxial Compression - Ben-Guo He; Lei Wang; Xia-Ting Feng; Rong-Li Zhen (Rock Mechanics and Rock Engineering, 2023)

Dose effects of restorer gene modulate pollen fertility in cotton CMS-D2 restorer lines via auxin signaling and flavonoid biosynthesis - Rong Zang; Kashif Shahzad; Xuexian Zhang; Liping Guo; Tingxiang Qi; Huini Tang; Ruijie Wang; Hailin Wang; Xiuqin Qiao; Meng Zhang; Jianyong Wu; Chaozhu Xing (Plant Cell Reports, 2023)

Effect of iron-loaded sludge biochar amendments on phytoremediation potential of Cr-contaminated soils by Leersia hexandra swartz - Jin-Chao Wang; Ji-Rong Zhao; Qing-Xia Huang; Li-Jiao Yang; Guo Yu; Yu-Feng Xu; Li-Heng Liu (Chemosphere, 2023)

Lack of the CCT domain changes the ability of mango MiCOL14A to resist salt and drought stress in Arabidopsis - Shu-Quan Chen; Cong Luo; Yuan Liu; Rong-Zhen Liang; Xing Huang; Ting-Ting Lu; Yi-Hang Guo; Ruo-Yan Li; Chu-Ting Huang; Zhuo Wang; Xin-Hua He (Plant Science, 2023)

Cretaceous magmatic migration and flare-up in Pamir–Karakoram - Xin Ma; Wei Dan; Jian Wang; Qiang Wang; Guo-Rong Tang; Mustafo Gadoev; Ilhomjon Oimahmadov; Gong-Jian Tang (Lithos, 2023)

Inactivation of airborne pathogenic microorganisms by plasma-activated nebulized mist - Li Guo; Pengyu Zhao; Yikang Jia; Zifeng Wang; Min Chen; Hao Zhang; Dingxin Liu; Yong Zhang; Xiaohua Wang; Mingzhe Rong (Journal of Hazardous Materials, 2023)

Interfacial permeation preparation of ZIF-8 in reactive deep eutectic for efficient adsorption and selective removal of Congo red - Yiwen Li; Huanhuan Zhang; Shikuan Xu; Yangyang Wang; Qi Guo; Rong Li; Yanjun Xing (Journal of Environmental Chemical Engineering, 2023)

Regulating dynamic equilibrium of active hydrogen for super-efficient nitrate electroreduction to ammonia - Yang Gao; Rong Wang; Yudong Li; Enshan Han; Maosen Song; Ziyi Yang; Feng Guo; Yanzhen He; Xiaohui Yang (Chemical Engineering Journal, 2023)

Characterization of the fragmented mitochondrial genome of domestic pig louse Haematopinus suis (Insecta: Haematopinidae) from China - Rong Li; Yu Nie; Yi-Tian Fu; Yuan-Ping Deng; Wei Wang; Ping-Ping Ma; Guo-Hua Liu (Systematic Parasitology, 2023)

Freeze-thaw treatment of bacteria significantly affects bacterial transport behaviors in both saturated and unsaturated porous media: Deep investigation the roles of flagella and extracellular polymeric substances - Lei He; Jianmei Qin; Jia Guo; Shuai Wang; Haifeng Rong; Meiping Tong (Science of The Total Environment, 2023)

Phloroglucinol derivatives, coumarins and an alkaloid from the roots of Evodia lepta Merr. - Xiao-Ying Ding; Jun-Ru Wen; Wei-Yao Lin; Guo-Yong Huang; Qian Feng; Lixin Duan; Shi-Jie Zhang; Zhongqiu Liu; Rong-Rong Zhang; Ying Wang (Phytochemistry, 2023)

Fabrication of a novel antioxidant emulsifier through tuning the molecular interaction between soy protein isolates and young apple polyphenols - Zhi Chao Song; Huan Zhang; Peng Fei Niu; Lin Shan Shi; Xue Yan Yang; Yong Hong Meng; Xiao Yu Wang; Tian Gong; Yu Rong Guo (Food Chemistry, 2023)

Black phosphorus quantum dots induced ferroptosis in lung cell via increasing lipid peroxidation and iron accumulation - Liangding Dou; Rong Liu; Zhaojizhe Wang; Zhi Huang; Lei Wang; Mo Lin; Xin Hou; Jinwen Zhang; Tantan Cheng; Qi He; Dai Wang; Dongbei Guo; et al. (Food and Chemical Toxicology, 2023)

Experimental investigation of the seismic resistance of RC beam–column connections after freeze–thaw cycle treatment - Xian-Liang Rong; Lei Li; Wei-Yuan Huang; Li-Guo Dong; Shan-Suo Zheng; Feng Wang; Dong Lu; Jun-Yan Wang (Engineering Structures, 2023)

Simultaneous removal of sulfamethoxazole during fermentative production of short-chain fatty acids - Yue Wang; Rongrong Lin; Yushuang Cao; Shuangfei Li; Rong Cui; Wanqian Guo; Shih-Hsin Ho; Yoong Kit Leong; Duu-Jong Lee; Jo-Shu Chang (Bioresource Technology, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

Heavy metal(loid)s in agriculture soils, rice, and wheat across China: Status assessment and spatiotemporal analysis - Cheng-Chen Wang; Qiao-Chu Zhang; Chang-An Yan; Guo-Yong Tang; Meng-Yan Zhang; Lena Q. Ma; Rong-Hui Gu; Ping Xiang (Science of The Total Environment, 2023)

Towards advanced mariculture wastewater treatment by bacterial-algal symbiosis system with different bacteria and algae inoculation ratios - Hongwei Rong; Yingying Li; Jingyin Wang; Qi Zhang; Baihui Cui; Dabin Guo (Journal of Water Process Engineering, 2023)

Clean treatment and resource utilization of oilfield wastewater using supercritical water gasification - Zhiyong Peng; Jialing Xu; Siqi Rong; Mingyi Zhang; Le Wang; Hui Jin; Liejin Guo (Journal of Cleaner Production, 2023)

Preparation and mechanism of carbon felt supported iron trioxide and zero-valent iron for enhancing anaerobic digestion performance - Zheng-Wei Wang; Chun-Hai WEI; Hua-Rong Yu; Fang-Shu Qu; Hong-Wei Rong; Jun-Guo He; Guang-Li Liu; Xia Huang; Huu Hao Ngo (Chemical Engineering Journal, 2023)

Characteristics of drought, low temperature, and concurrent events of maize in Songliao Plain - Yunmeng Zhao; Ying Guo; Rui Wang; Kaiwei Li; Guangzhi Rong; Jiquan Zhang; Chunli Zhao (International Journal of Climatology, 2023)
Maize is susceptible to drought and low temperatures. In recent years, drought, low temperatures, and their composite events have often occurred during the growth period of maize, causing a huge impact. In this study, maize in the Songliao Plain was used as the research object. Based on the crop water surplus deficit index (CWSDI) and heat index (F(T)), combined with the Theil–Sen median and Mann–Kendall tests (Sen–MK) and empirical orthogonal function (EOF), the temporal trends and spatial patterns of drought and low temperatures in different growth periods of maize were obtained. Copula modelling was used to analyse the joint probability distribution and return period of drought and low temperatures. The results showed that the temporal variation trend of the CWSDI was significantly different at different growth periods of maize, and there were different trends and spatial modal distributions. However, the temporal variation trend of F(T) was similar, showing a downward trend over the entire region. There was no obvious asymmetry or skew‐dependent structure in the distribution of concurrent events of drought and low temperature; however, the joint probability contours of different growth periods were biased to the upper left. The recurrence period of drought and low‐temperature concurrent events was within 2 years, and the recurrence period was basically between 2 and 5 years, with a reduction in drought or low temperatures.

Divergence in the distribution of di(2-ethylhexyl) phthalate (DEHP) in two soils - Qiutang Wang; Yanwen Xu; Wenchao Du; Ying Yin; Xuan Wu; Feifei Sun; Rong Ji; Hongyan Guo (Environmental Science and Pollution Research, 2023)

Black phosphorus quantum dots induce autophagy and apoptosis of human bronchial epithelial cells via endoplasmic reticulum stress - Lei Wang; Mo Lin; Xin Hou; Liangding Dou; Zhi Huang; Rong Liu; Jinwen Zhang; Chuchu Cai; Chen Chen; Ying Liu; Dai Wang; Dongbei Guo; et al. (Chemosphere, 2023)

A green aqueous foam stabilized by cellulose nanofibrils and camellia saponin for geological CO2 sequestration - Qichao Lv; Tongke Zhou; Yingting Luan; Rong Zheng; Xinshu Guo; Xiaoming Wang; Abdolhossein Hemmati-Sarapardeh (Journal of Cleaner Production, 2023)

Inactivation of Salmonella enteritidis on the surface of eggs by air activated with gliding arc discharge plasma - Li Guo; Pengyu Zhao; Zhiqian Yao; Tianhui Li; Mengying Zhu; Zifeng Wang; Lingling Huang; Gulimire Niyazi; Dingxin Liu; Mingzhe Rong (Food Control, 2023)

Engineering single-atom catalysts as multifunctional polysulfide and lithium regulators toward kinetically accelerated and durable lithium-sulfur batteries - Donghua Wang; Kaikai Ma; Jiamao Hao; Wenyuan Zhang; Haofeng Shi; Chengdeng Wang; Zhihao Xiong; Zhiming Bai; Fu-Rong Chen; Junjie Guo; Bingshe Xu; Xiaoqin Yan; et al. (Chemical Engineering Journal, 2023)

Chinese version of the auditory verbal learning test: normative study and clinical applications in Chinese-speaking population in Shijiazhuang city - Fang-Ming Dong; Wei Wang; Shang-Zun Guo; Kai Shao; Ya-Xue Song; Ning Han; Yan-Li Jia; Rong-Fang Feng; Jian-Hua Wang (Acta Neurologica Belgica, 2023)

Corrigendum to “Promotional effects of calcination temperature and H2O on the catalytic activity of Al-substituted MnAlO catalysts for low-temperature acetone oxidation” [Chemosphere 301 (2022) 134722] - Wan-Peng Zhang; Kun Wu; Junyi Zhao; Jun He; Leiping Wang; Hang Xiao; Jian-Bing Guo; Jian-Rong Li (Chemosphere, 2023)

CircBCL11B acts as a ceRNA to facilitate 1,2-dichloroethane-induced astrocyte swelling via miR-29b-3p/AQP4 axis in SVG p12 cells - Yizhou Zhong; Bingli Zhang; Yuji Huang; Jiaxin Du; Boxuan Liang; Zhiming Li; Rongyi Ye; Bo Wang; Hongyi Xian; Xifei Yang; Weifeng Rong; Xiang Guo; et al. (Toxicology Letters, 2023)

Quantum neuronal sensing of quantum many-body states on a 61-qubit programmable superconducting processor - Ming Gong; He-Liang Huang; Shiyu Wang; Chu Guo; Shaowei Li; Yulin Wu; Qingling Zhu; Youwei Zhao; Shaojun Guo; Haoran Qian; Yangsen Ye; Chen Zha; et al. (Science Bulletin, 2023)

Virulence assessment of four Glaesserella parasuis strains isolated in Liaoning province of China - Ping Yan; Yong C. Jia; Xue L. Zhang; Yuan Y. Zhou; Ying Guo; Rong L. Yin; Jing Yuan; Lin X. Wang; Zhong B. Guo; Jing Y. Wang; Xin Wang; Rong H. Yin (Research in Veterinary Science, 2023)

SlGH3.15, a member of the GH3 gene family, regulates lateral root development and gravitropism response by modulating auxin homeostasis in tomato - Guo Ai; Rong Huang; Dedi Zhang; Miao Li; Guobin Li; Wangfang Li; John K. Ahiakpa; Yikui Wang; Zonglie Hong; Junhong Zhang (Plant Science, 2023)

Elevated CO2 alleviated the dissemination of antibiotic resistance genes in sulfadiazine-contaminated soil: A free-air CO2 enrichment study - Meiling Xu; Qian Xiang; Fen Xu; Lei Guo; Laura J. Carter; Wenchao Du; Chunwu Zhu; Ying Yin; Rong Ji; Xiaozhi Wang; Hongyan Guo (Journal of Hazardous Materials, 2023)

Phytoplankton community changes in a coastal upwelling system during the last century - Peng Peng; Rong Bi; Julian P. Sachs; Jie Shi; Yifei Luo; Weifang Chen; Chih-An Huh; Meng Yu; Yali Cao; Yaoyao Wang; Zhong Cao; Xiaohan Bao; et al. (Global and Planetary Change, 2023)

Identification of Heterophilic Epitopes of H1N1 Influenza Virus Hemagglutinin - Jing-ying Sun; Chun-yan Guo; Guo-rong Wang; Li-ting Yan; Qing Feng; Yan Li; Xue-ping Huo; Xin Xie; Jun Hu; Li-jun Sun (Current Microbiology, 2023)

Interaction Between the Glymphatic System and α-Synuclein in Parkinson’s Disease - Yu Zhang; Cui Zhang; Xu-Zhong He; Zhen-Hua Li; Jing-Cai Meng; Rui-Ting Mao; Xin Li; Rong Xue; Qian Gui; Guo-Xing Zhang; Lin-Hui Wang (Molecular Neurobiology, 2023)

The phosphorus harvest from low-temperature mainstream wastewater through iron phosphate crystallization in a pilot-scale partial nitritation/anammox reactor - Yan Guo; Eli Hendrik Sanjaya; Tianjie Wang; Chao Rong; Zibin Luo; Yi Xue; Hong Chen; Yu-You Li (Science of The Total Environment, 2023)

Efficient inactivation of the contamination with pathogenic microorganisms by a combination of water spray and plasma-activated air - Li Guo; Pengyu Zhao; Yikang Jia; Tianhui Li; Lingling Huang; Zifeng Wang; Dingxin Liu; Zhanwu Hou; Yizhen Zhao; Lei Zhang; Hua Li; Yu Kong; et al. (Journal of Hazardous Materials, 2023)

Achieving ultrahigh energy storage properties with superior stability in novel (Ba(1-)Bi )(Ti(1-)Zn0.5Sn0.5)O3 relaxor ferroelectric ceramics via chemical modification - Ming Yin; Guang-Jian Bai; Peng Li; Ji-Gong Hao; Wei Li; Wei-Fang Han; Yu-Chao Li; Chun-Ming Wang; Guo-Rong Li; Peng Fu (Chemical Engineering Journal, 2023)

A chitin synthase mutation confers widespread resistance to buprofezin, a chitin synthesis inhibitor, in the brown planthopper, Nilaparvata lugens - Bin Zeng; Fu-Rong Chen; Ya-Ting Liu; Di Guo; Yi-Jie Zhang; Ze-Rui Feng; Li-Xiang Wang; John Vontas; Shun-Fan Wu; Kun Yan Zhu; Cong-Fen Gao (Journal of Pest Science, 2023)

Diagnosis of atmospheric circulation shifts in the central Tibetan Plateau: Evidence from stable isotopes - Yao Li; Wusheng Yu; Lide Tian; Stephen Lewis; Kei Yoshimura; Cheng Wang; Jiangpeng Cui; Yaoming Ma; Rong Guo; Jingyi Zhang; Zhaowei Jing; Lili Shao; et al. (Atmospheric Research, 2023)

A near-infrared fluorescent probe for monitoring abnormal mitochondrial viscosity in cancer and fatty-liver mice model - Jing-Jing Chao; Hui Zhang; Zhi-Qing Wang; Qiao-Rong Liu; Guo-Jiang Mao; Dong-Hua Chen; Chun-Yan Li (Analytica Chimica Acta, 2023)

Proactive therapeutic drug monitoring of vincristine in pediatric and adult cancer patients: current supporting evidence and future efforts - Chun-Ying Wu; Guan-Ting Li; Chen-Chao Chu; Hong-Li Guo; Wei-Rong Fang; Tao Li; Yong-Ren Wang; Jing Xu; Ya-Hui Hu; Li Zhou; Feng Chen (Archives of Toxicology, 2023)

Zinc finger protein 671 has a cancer-inhibiting function in colorectal carcinoma via the deactivation of Notch signaling - Yan Wang; Fen-rong Chen; Chong-cao Wei; Lin-lang Sun; Chen-yu Liu; Long-bao Yang; Xiao-yan Guo (Toxicology and Applied Pharmacology, 2023)

Concentrations, congener patterns, and correlations of unintentional persistent organic pollutants in cement kilns co-processing hazardous waste - Changzhi Chen; Haoyang Wang; Guorui Liu; Bingcheng Lin; Lili Yang; Rong Jin; Yuxiang Sun; Jianping Guo; Yinming Li; Nan Yang; Aihong Li; Changliang Li; et al. (Science of The Total Environment, 2023)

A study on molecular structural evolution of type II kerogen in a gold tube thermal system: Insights from solid-state 13C NMR - Deping Zhang; Huairen Cao; Yan Lei; Hao Wu; Xiaoyu Wang; Xuelian Guo; Jianping Yan; Shuhua Wang; Tianchi Shi; Haolin Li; Yan-rong Zou; Ping'an Peng (Fuel, 2023)

Elevated CO2 aggravated polystyrene microplastics effects on the rice-soil system under field conditions - Meiling Xu; Qiao Xu; Guobing Wang; Wenchao Du; Jianguo Zhu; Ying Yin; Rong Ji; Xiaozhi Wang; Hongyan Guo (Environmental Pollution, 2023)

Construction of 3D Ni2+-Al3+-LDH/γ-Fe2O3-Cd2+-Ni2+-Fe3+-LDH structures and multistage recycling treatment of dye and fluoride-containing wastewater - Rui Dang; Xiang-Rong Ma; Yun-Peng Zhao; Menjiao Ren; Wei Guo; Yu-Hong Kang; Yong Gao; Shiqing Bi; Wenwen Gao; Hua-Rui Hao; Rui Bai; Yu-Fei Wang; et al. (Chemical Engineering Journal, 2023)

Extracellular Mitochondria Activate Microglia and Contribute to Neuroinflammation in Traumatic Brain Injury - Chaonan Zhang; Chuan Liu; Fanjian Li; Mutian Zheng; Yafan Liu; Lei Li; Huaijin Yang; Shu Zhang; Chongjin Wang; Hongtao Rong; Hui Guo; Ying Li; et al. (Neurotoxicity Research, 2022)

Study on the Relationship Between Diet, Physical Health and Gut Microflora of Chinese College Students - Xiafen Hu; Jiaqi Guo; Jiadun Wang; Wanxin Liu; Xiaochen Xiang; Siyang Chen; Xinquan Li; Jinhan Tang; Wei Zhang; Hui Chen; Rong Shu; Qingming Wu; et al. (Current Microbiology, 2022)

Similarity of the turbulent kinetic energy dissipation rate distribution in the upper mixed layer of the tropical Indian Ocean - Xian-Rong Cen; Shuang-Xi Guo; Yan Wang; Sheng-Qi Zhou (Frontiers in Marine Science, 2022)
Turbulence within the upper ocean mixed layer plays a key role in various physical, biological, and chemical processes. Between September and November 2011, a dataset of 570 vertical profiles of the turbulent kinetic energy (TKE) dissipation rate, as well as conventional hydrological and meteorological data, were collected in the upper layer of the tropical Indian Ocean. These data were used to statistically analyze the vertical distribution of the TKE dissipation rate in the mixed layer. The arithmetic-mean method made the statistical TKE dissipation rate profile more scattered than the median and geometric-mean methods. The statistical TKE dissipation rate were respectively scaled by the surface buoyancy flux and the TKE dissipation rate at the mixed-layer base. It was found that the TKE dissipation rate scaled by that at the mixed-layer base exhibited better similarity characteristics than that scaled by the surface buoyancy flux, whether the stability parameter D /| L MO | was greater or less than 10, indicating that the TKE dissipation rate at the mixed-layer base is a better characteristic scaling parameter for reflecting the intrinsic structure of the TKE dissipation rate in the mixed layer, where D and L MO are respectively the mixed-layer thickness and the Monin-Obukhov length scale. The parameterization of the TKE dissipation rate at the mixed-layer base on the shear-driven dissipation rate and the surface buoyancy flux was further explored. It was found that the TKE dissipation rate at the mixed-layer base could be well fitted by a linear combination of three terms: the wind-shear-driven dissipation rate, the surface buoyancy flux, and a simple nonlinear coupling term of these two .

Expression patterns and correlation analyses of muscle-specific genes in the process of sheep myoblast differentiation - Hejie Wang; Minmin Dou; Jun Li; Peng Cao; Junling Li; Tianyan Guo; Dipeng Zhao; Ajab Khan; Yingliang Li; Baojun Li; Jian Qin; Rong Du (In Vitro Cellular & Developmental Biology - Animal, 2022)

Identification of resistance of Guangxi (Oryza rufipogon Griff.) to white-backed planthopper with stem evaluation method - Xin-ying Guo; Xuan Wang; Liang Luo; Yao-yu Fang; Kai-chong Teng; Neng Zhao; Jin-lian Yang; Fang Liu; Bao-xiang Qin; Ji-jing Luo; Rong-bai Li (Genetic Resources and Crop Evolution, 2022)

Crustal Contamination of the Mantle-Derived Liuyuan Basalts: Implications for the Permian Evolution of the Southern Central Asian Orogenic Belt - Yuanyang Yu; Keqing Zong; Yu Yuan; Reiner Klemd; Xin-Shui Wang; Jingliang Guo; Rong Xu; Zhaochu Hu; Yongsheng Liu (Journal of Earth Science, 2022)

Transmission of SARS-CoV-2 on Cold-Chain Food: Precautions Can Effectively Reduce the Risk - Meiyue Guo; Junfeng Yan; Yuan Hu; Lu Xu; Jinling Song; Kun Yuan; Xiangru Cheng; Sui Ma; Jie Liu; Xianbing Wu; Liegang Liu; Shuang Rong; et al. (Food and Environmental Virology, 2022)

Erratum to: Temporal changes in wetland plant communities with decades of cumulative water pollution in two plateau lakes in China’s Yunnan Province - Si-hai Wang; Chao Wu; De-rong Xiao; Juan Wang; Xi-ping Cheng; Fang-bin Guo (Journal of Mountain Science, 2022)

Impact of heat stress on milk yield, antioxidative levels, and serum metabolites in primiparous and multiparous Holstein cows - Xue Chen; Jia Nan Dong; Ji Ye Rong; Jun Xiao; Wei Zhao; Natnael D. Aschalew; Xue Feng Zhang; Tao Wang; Gui Xin Qin; Zhe Sun; Yu Guo Zhen (Tropical Animal Health and Production, 2022)

Simulation of Urban Land Expansion Under Ecological Constraints in Harbin-Changchun Urban Agglomeration, China - Rong Guo; Tong Wu; Xiaochen Wu; Stendardo Luigi; Yueqin Wang (Chinese Geographical Science, 2022)

How do precipitation events modify the stable isotope ratios in leaf water at Lhasa on the southern Tibetan Plateau? - Yong Wang; Wusheng Yu; Lun Luo; Minghui Li; Xiaoming Liu; Rong Guo; Yaoming Ma; Baiqing Xu; Guangjan Wu; Chengyi Zhao; Zhaowei Jing; Feili Wei; et al. (Isotopes in Environmental and Health Studies, 2022)

Cassiterite oxygen isotopes in magmatic-hydrothermal systems: in situ microanalysis, fractionation factor, and applications - Yang Li; Sheng He; Rong-Qing Zhang; Xian-Wu Bi; Lian-Jun Feng; Guo-Qiang Tang; Wen-Zhong Wang; Fang Huang; Xian-Hua Li (Mineralium Deposita, 2022)

Bioactive isocoumarins isolated from a mangrove-derived fungus Penicillium sp. MGP11 - Rong-Qing Mei; Bin Wang; Wei-Nv Zeng; Guo-Lei Huang; Guang-Ying Chen; Cai-Juan Zheng (Natural Product Research, 2022)

QTL mapping integrated with BSA-Seq analysis identifies a novel gene conferring resistance to brown planthopper from common wild rice (Oryza rufipogon Griff.) - Xuan Wang; Yue Han; Yue-xiong Zhang; Biao Deng; Bi-qiu Wu; Xin-ying Guo; Yu-fen Qin; Yao-yu Fang; Fang Liu; Bao-xiang Qin; Ji-jing Luo; Rong-bai Li (Euphytica, 2022)

Digoxin Ameliorates Glymphatic Transport and Cognitive Impairment in a Mouse Model of Chronic Cerebral Hypoperfusion - Jie Cao; Di Yao; Rong Li; Xuequn Guo; Jiahuan Hao; Minjie Xie; Jia Li; Dengji Pan; Xiang Luo; Zhiyuan Yu; Minghuan Wang; Wei Wang (Neuroscience Bulletin, 2022)

Mass cultivation of conidia of Pyricularia oryzae - Zhong-na Hao; Hai-ping Qiu; Zhen Zhang; Rong-yao Chai; Shi-zhen Wang; Yan-li Wang; Jiao-yu Wang; Guo-chang Sun (Journal of Plant Pathology, 2022)

Control of chronic obstructive pulmonary disease in urban populations: findings from a cross-sectional prevalence survey in Shenzhen, China - Le-Cai Ji; Jin-Feng Yin; Chun-Rong Lu; Hong-Yun Guan; Wei-Guo Tan; Ling-Wei Wang; Qi Jiang (Environmental Science and Pollution Research, 2022)

Epidemiological investigation and genetic characterization of porcine astrovirus genotypes 2 and 5 in Yunnan province, China - Keqing Ren; Rong Wang; Xiao Liu; Yinghua Liu; Jintao Zhang; Junyu Bi; Lianfeng Zhao; Zhigang Guo; Jianping Liu; Gefen Yin (Archives of Virology, 2022)

Caffeine Inhibits Activation of the NLRP3 Inflammasome via Autophagy to Attenuate Microglia-Mediated Neuroinflammation in Experimental Autoimmune Encephalomyelitis - Hui-Qi Wang; Kai-Yi Song; Jin-Zhou Feng; Si-Yuan Huang; Xiu-Ming Guo; Lei Zhang; Gang Zhang; Ying-Chao Huo; Rong-Rong Zhang; Yue Ma; Qing-Zhe Hu; Xin-Yue Qin (Journal of Molecular Neuroscience, 2022)

Promotional effect of ZrO2 and WO3 on bimetallic Pt-Pd diesel oxidation catalyst - Rongrong Fan; Zhaoqiang Li; Yu Wang; Yan Wang; Zhiyong Ding; Cheng Zhang; Na Kang; Xin Guo; Rong Wang (Environmental Science and Pollution Research, 2022)

Stress response mechanisms and description of three novel species Shewanella avicenniae sp. nov., Shewanella sedimentimangrovi sp. nov. and Shewanella yunxiaonensis sp. nov., isolated from mangrove ecosystem - Guo-Hong Liu; Qi Zhang; Manik Prabhu Narsing Rao; Shang Yang; Rong Tang; Huai Shi; Jie-Ping Wang; Guan-Min Huang; Bo Liu; Shun-Gui Zhou; Wen-Jun Li (Antonie van Leeuwenhoek, 2021)

Use of historical and contemporary distribution of mammals in China to inform conservation - Kang Huang; He Zhang; Chengliang Wang; Rong Hou; Pei Zhang; Gang He; Songtao Guo; Shiyi Tang; Baoguo Li; Charles Oxnard; Ruliang Pan (Conservation Biology, 2021)
A systematic understanding of dynamic animal extinction trajectories for different regions in a nation like China is critically important to developing practical conservation strategies. We explored historical and contemporary changes in terrestrial mammalian diversity to determine how diversity in each of the 5 regions in China has changed over time and to examine the conservation potential of these regions. We used records from databases on Pleistocene mammalian fossils and historical distribution records (1175–2020) for Primates (as a case study) to reconstruct evolutionary and historical distribution trajectories of the 11 orders of terrestrial mammals and to predict their prospective survival based on the national conservation strategy applied. The results indicated that since the Pleistocene, 4–5 mammalian orders have been lost in the northeast, 3 in central China, 2 along the coast, and 1 in the northwest. In the southwest, all 11 orders were maintained. Contemporarily, the coast and southwest had the highest and second‐highest species densities. The southwest region and southeastern sections of the northwest region were the most historically and contemporarily diverse areas, which suggests that they should be the first priority for protected area (PA) designation. The central and coastal areas should be secondarily prioritized. In these 2 regions, conservation should focus on human coexistence with nature. Less attention should be paid to the PA in the northeast and western northwest because in these areas ecosystems are depauperate and the climate is harsh. Conservation in these areas should focus principally on avoiding further human encroachment on natural areas. Article impact statement : Historical and contemporary patterns of extinction can be a basis for mammalian conservation strategies.

Effects of Gap Resonance on the Hydrodynamics and Dynamics of a Multi-Module Floating System with Narrow Gaps - Mingsheng Chen; Hongrui Guo; Rong Wang; Ran Tao; Ning Cheng (Journal of Marine Science and Engineering, 2021)
Multi-module floating system has attracted much attention in recent years as ocean space utilization becomes more demanding. This type of structural system has potential applications in the design and construction of floating piers, floating airports and Mobile Offshore Bases (MOBs) generally consists of multiple modules with narrow gaps in which hydrodynamic interactions play a non-neglected role. This study considers a numerical model consisting of several rectangular modules to study the hydrodynamics and dynamics of the multi-module floating system subjected to the waves. Based on ANSYS-AQWA, both frequency-domain and time-domain simulations are performed to analyze the complex multi-body hydrodynamic interactions by introducing artificial damping on the gap surfaces. Parametric studies are carried out to investigate the effects of the gap width, shielding effects of the multi-body system, artificial damping ratio on the gap surface, and the dependency of the hydrodynamic interaction effect on wave headings is clarified. Based on the results, it is found that the numerical analysis based on the potential flow theory with artificial damping introduced can produce accurate results for the normal wave period range. In addition, the effects of artificial damping on the dynamics and connector loads are investigated by using a simplified RMFC model. For the case of adding an artificial damping ratio of 0.2, the relative heave and pitch motions are found to be reduced by 33% and 50%, respectively. In addition, the maximum cable and fender forces are found to be reduced by 50%, compared with the case without viscosity correction.

One new α , β -unsaturated 7-ketone sterol from the mangrove-derived fungus Phomopsis sp.MGF222 - Xiao-Chen Zhu; Guo-Lei Huang; Rong-Qing Mei; Bin Wang; Xue-Ping Sun; You-Ping Luo; Jing Xu; Cai-Juan Zheng (Natural Product Research, 2021)

A new phenol derivative isolated from mangrove-derived fungus Eupenicillium sp. HJ002 - Rong-Qing Mei; Xu-Hua Nong; Bin Wang; Xue-Ping Sun; Guo-Lei Huang; You-Ping Luo; Cai-Juan Zheng; Guang-Ying Chen (Natural Product Research, 2021)

Differences in pathogenicity and physiologic races between Pyricularia oryzae isolates from indica and japonica rice varieties - Zhong-na Hao; Zhen Zhang; Hai-ping Qiu; Rong-yao Chai; Shi-zhen Wang; Yan-li Wang; Jiao-yu Wang; Guo-chang Sun (Journal of Plant Pathology, 2021)

Mortality risk attributable to diurnal temperature range: a multicity study in Yunnan of southwest China - Yujin Wang; Yang Chen; Jiaqi Chen; Rong Wu; Pi Guo; Shun Zha; Qingying Zhang (Environmental Science and Pollution Research, 2021)

Lignans and phenylpropanoids from the liquid juice of phyllostachys edulis - De-Tao Wang; Ying-Ying Xue; Ying-Fang Zhang; Hang Xun; Qi-Rong Guo; Feng Tang; Jia Sun; Fei-Fei Qi (Natural Product Research, 2021)

Phenomic and metabolomic responses of roots to cadmium reveal contrasting resistance strategies in two rice cultivars (Oryza sativa L.) - Chong Liu; Mo-ming Lan; Er-kai He; Ai-jun Yao; Guo-bao Wang; Ye-tao Tang; Rong-liang Qiu (Soil Ecology Letters, 2021)

LncRNA-MEG3 Regulates the Inflammatory Responses and Apoptosis in Porcine Alveolar Macrophages Infected with Haemophilus parasuis Through Modulating the miR-210/TLR4 Axis - Rong H. Yin; Zhong B. Guo; Yuan Y. Zhou; Chao Wang; Rong L. Yin; Wen L. Bai (Current Microbiology, 2021)

Bi-allelic BRWD1 variants cause male infertility with asthenoteratozoospermia and likely primary ciliary dyskinesia - Ting Guo; Chao-Feng Tu; Dan-Hui Yang; Shui-Zi Ding; Cheng Lei; Rong-Chun Wang; Lv Liu; Xi Kang; Xiao-Qing Shen; Yi-Feng Yang; Zhi-Ping Tan; Yue-Qiu Tan; et al. (Human Genetics, 2021)

Isolation and Identification of Pseudomonas sp. Strain DY-1 from Agricultural Soil and Its Degradation Effect on Prometryne - Dong Liang; Ming-yue Ding; Chang-yixin Xiao; Ya-wen Shen; Yin-yue Wang; Hai-tao Li; Rong-mei Liu; Ji-guo Gao (Current Microbiology, 2021)

MiR-150-5p regulate T cell activation in severe aplastic anemia by targeting Bach2 - Yingmei Li; Jifeng Yu; Fang Wang; Rong Guo; Haizhou Xing; Yali Chen; Dandan Chen; Xinsheng Xie; Dingming Wan; Zhongxing Jiang (Cell and Tissue Research, 2021)

Genome-wide identification and characterization of long non-coding RNAs involved in flag leaf senescence of rice - Xiaoping Huang; Hongyu Zhang; Qiang Wang; Rong Guo; Lingxia Wei; Haiyan Song; Weigang Kuang; Jianglin Liao; Yingjin Huang; Zhaohai Wang (Plant Molecular Biology, 2021)
Key message This study showed the systematic identification of long non-coding RNAs (lncRNAs) involving in flag leaf senescence of rice, providing the possible lncRNA-mRNA regulatory relationships and lncRNA-miRNA-mRNA ceRNA networks during leaf senescence. Abstract LncRNAs have been reported to play crucial roles in diverse biological processes. However, no systematic identification of lncRNAs associated with leaf senescence in plants has been studied. In this study, a genome-wide high throughput sequencing analysis was performed using rice flag leaves developing from normal to senescence. A total of 3953 lncRNAs and 38757 mRNAs were identified, of which 343 lncRNAs and 9412 mRNAs were differentially expressed. Through weighted gene co-expression network analysis (WGCNA), 22 continuously down-expressed lncRNAs targeting 812 co-expressed mRNAs and 48 continuously up-expressed lncRNAs targeting 1209 co-expressed mRNAs were considered to be significantly associated with flag leaf senescence. Gene Ontology results suggested that the senescence-associated lncRNAs targeted mRNAs involving in many biological processes, including transcription, hormone response, oxidation–reduction process and substance metabolism. Additionally, 43 senescence-associated lncRNAs were predicted to target 111 co-expressed transcription factors. Interestingly, 8 down-expressed lncRNAs and 29 up-expressed lncRNAs were found to separately target 12 and 20 well-studied senescence-associated genes (SAGs). Furthermore, analysis on the competing endogenous RNA (CeRNA) network revealed that 6 down-expressed lncRNAs possibly regulated 51 co-expressed mRNAs through 15 miRNAs, and 14 up-expressed lncRNAs possibly regulated 117 co-expressed mRNAs through 21 miRNAs. Importantly, by expression validation, a conserved miR164-NAC regulatory pathway was found to be possibly involved in leaf senescence, where lncRNA MSTRG.62092.1 may serve as a ceRNA binding with miR164a and miR164e to regulate three transcription factors. And two key lncRNAs MSTRG.31014.21 and MSTRG.31014.36 also could regulate the abscisic-acid biosynthetic gene BGIOSGA025169 ( OsNCED4 ) and BGIOSGA016313 (NAC family) through osa-miR5809. The possible regulation networks of lncRNAs involving in leaf senescence were discussed, and several candidate lncRNAs were recommended for prior transgenic analysis. These findings will extend the understanding on the regulatory roles of lncRNAs in leaf senescence, and lay a foundation for functional research on candidate lncRNAs.

Involvement of Mitophagy in Aluminum Oxide Nanoparticle–Induced Impairment of Learning and Memory in Mice - Tao Huang; Weiwei Guo; Yanhong Wang; Lijun Chang; Nan Shang; Jin Chen; Rong Fan; Lan Zhang; Xiaocheng Gao; Qiao Niu; Qinli Zhang (Neurotoxicity Research, 2021)

Carbon monoxide-triggered health effects: the important role of the inflammasome and its possible crosstalk with autophagy and exosomes - Rong-Jane Chen; Yu-Hsuan Lee; Tzu-Hao Chen; Yu-Ying Chen; Ya-Ling Yeh; Ching-Ping Chang; Chien-Cheng Huang; How-Ran Guo; Ying-Jan Wang (Archives of Toxicology, 2021)

Effects of simulated drought stress on carotenoid contents and expression of related genes in carrot taproots - Rong-Rong Zhang; Ya-Hui Wang; Tong Li; Guo-Fei Tan; Jian-Ping Tao; Xiao-Jun Su; Zhi-Sheng Xu; Yong-Sheng Tian; Ai-Sheng Xiong (Protoplasma, 2021)

Systematic identification and characterization of circular RNAs involved in flag leaf senescence of rice - Xiaoping Huang; Hongyu Zhang; Rong Guo; Qiang Wang; Xuanzhi Liu; Weigang Kuang; Haiyan Song; Jianglin Liao; Yingjin Huang; Zhaohai Wang (Planta, 2021)
Main conclusion Circular RNAs (circRNAs) identification, expression profiles, and construction of circRNA-parental gene relationships and circRNA-miRNA-mRNA ceRNA networks indicate that circRNAs are involved in flag leaf senescence of rice. Abstract Circular RNAs (circRNAs) are a class of 3′-5′ head-to-tail covalently closed non-coding RNAs which have been proved to play important roles in various biological processes. However, no systematic identification of circRNAs associated with leaf senescence in rice has been studied. In this study, a genome-wide high-throughput sequencing analysis was performed using rice flag leaves developing from normal to senescence. Here, a total of 6612 circRNAs were identified, among which, 113 circRNAs were differentially expressed (DE) during the leaf senescence process. Moreover, 4601 (69.59%) circRNAs were derived from the exons or introns of their parental genes, while 2110 (71%) of the parental genes produced only one circRNA. The sequence alignment analysis showed that hundreds of rice circRNAs were conserved among different plant species. Gene Ontology (GO) enrichment analysis revealed that parental genes of DE circRNAs were enriched in many biological processes closely related to leaf senescence. Through weighted gene co-expression network analysis (WGCNA), six continuously down-expressed circRNAs, 18 continuously up-expressed circRNAs and 15 turn-point high-expressed circRNAs were considered to be highly associated with leaf senescence. Additionally, a total of 17 senescence-associated circRNAs were predicted to have parental genes, in which, regulations of three circRNAs to their parental genes were validated by qRT-PCR. The competing endogenous RNA (ceRNA) networks were also constructed. And a total of 11 senescence-associated circRNAs were predicted to act as miRNA sponges to regulate mRNAs, in which, regulation of two circRNAs to eight mRNAs was validated by qRT-PCR. It is discussed that senescence-associated circRNAs were involved in flag leaf senescence probably through mediating their parental genes and ceRNA networks, to participate in several well-studied senescence-associated processes, mainly including the processes of transcription, translation, and posttranslational modification (especially protein glycosylation), oxidation–reduction process, involvement of senescence-associated genes, hormone signaling pathway, proteolysis, and DNA damage repair. This study not only showed the systematic identification of circRNAs involved in leaf senescence of rice, but also laid a foundation for functional research on candidate circRNAs.

Overexpression of thioredoxin reductase 1 can reduce DNA damage, mitochondrial autophagy and endoplasmic reticulum stress in Parkinson's disease - Zihua Liu; Qiang Ye; Fang Wang; Yanan Guo; Rong Cui; Jianlin Wang; Degui Wang (Experimental Brain Research, 2021)

Risk of congenital heart disease due to exposure to common electrical appliances during early pregnancy: a case-control study - Doudou Zhao; Leqian Guo; Ruo Zhang; Qixia Zhu; Hongli Wang; Rong Liu; Hong Yan; Shaonong Dang (Environmental Science and Pollution Research, 2021)

Quantitative Determination of Glymphatic Flow Using Spectrophotofluorometry - Yu Zhang; Jian Song; Xu-Zhong He; Jian Xiong; Rong Xue; Jia-Hao Ge; Shi-Yu Lu; Die Hu; Guo-Xing Zhang; Guang-Yin Xu; Lin-Hui Wang (Neuroscience Bulletin, 2020)

Small grain and semi-dwarf 3, a WRKY transcription factor, negatively regulates plant height and grain size by stabilizing SLR1 expression in rice - Jie Lan; Qibing Lin; Chunlei Zhou; Yakun Ren; Xi Liu; Rong Miao; Ruonan Jing; Changling Mou; Thanhliem Nguyen; Xingjie Zhu; Qian Wang; Xin Zhang; et al. (Plant Molecular Biology, 2020)

Retraction Note to: Ambient air pollution and adverse birth outcomes: a systematic review and meta-analysis - Le-qian Guo; Yu Chen; Bai-bing Mi; Shao-nong Dang; Dou-dou Zhao; Rong Liu; Hong-li Wang; Hong Yan (Journal of Zhejiang University-SCIENCE B, 2020)

Crosstalk between PKC and MAPK pathway activation in cardiac fibroblasts in a rat model of atrial fibrillation - Wei-hua Guo; Xian Wang; Mei-sheng Shang; Zhe Chen; Qi Guo; Li Li; Hai-ying Wang; Rong-hui Yu; Chang-sheng Ma (Biotechnology Letters, 2020)

Microalgae for saline wastewater treatment: a critical review - Hoang Nhat Phong Vo; Huu Hao Ngo; Wenshan Guo; Soon Woong Chang; Dinh Duc Nguyen; Zhuo Chen; Xiaochang C. Wang; Rong Chen; Xinbo Zhang (Critical Reviews in Environmental Science and Technology, 2020)

Synthesis, pharmacological evaluation and molecular docking of novel R-/S-2-(2-hydroxypropanamido)-5-trifluoromethyl benzoic acid as dual anti-inflammatory anti-platelet aggregation agents - Rong Rong; Rui-zhen Zhang; Xin Wang; Yu-han Dan; Yun-li Zhao; Zhi-guo Yu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2020)

Down-regulation of lncRNA CASC9 aggravates sepsis-induced acute lung injury by regulating miR-195-5p/PDK4 axis - Huai-rong Wang; Xiu-yan Guo; Xin-yan Liu; Xuan Song (Inflammation Research, 2020)

Two new aromatic polyketides from a deep-sea fungus Penicillium sp. SCSIO 06720 - Cui Guo; Xiu-Ping Lin; Sheng-Rong Liao; Bin Yang; Xue-Feng Zhou; Xian-Wen Yang; Xin-Peng Tian; Jun-Feng Wang; Yong-Hong Liu (Natural Product Research, 2020)

Simulating Spatial Variation of Soil Carbon Content in the Yellow River Delta: Comparative Analysis of Two Artificial Neural Network Models - Chen Wang; Yuan Cui; Ziwen Ma; Yutong Guo; Qian Wang; Yujiao Xiu; Rong Xiao; Mingxiang Zhang (Wetlands, 2020)

Circadian gene Clock participates in mitochondrial apoptosis pathways by regulating mitochondrial membrane potential, mitochondria out membrane permeablization and apoptosis factors in AML12 hepatocytes - Shuhong Yang; Yanyou Liu; Yimei Guo; Rong Liu; Fang Qi; Xiaoxue Li; Hang Yu; Shuting Cheng; Zhengrong Wang (Molecular and Cellular Biochemistry, 2020)

Roles of moisture sources and transport in precipitation variabilities during boreal summer over East China - Qu-cheng Chu; Rong Zhi; Qi-guang Wang; Guo-lin Feng (Climate Dynamics, 2019)

Degradation of Bisphenol S by a Bacterial Consortium Enriched from River Sediments - Xingwang Wang; Jianqiu Chen; Rong Ji; Yanhua Liu; Yu Su; Ruixin Guo (Bulletin of Environmental Contamination and Toxicology, 2019)

Predicting trait-like individual differences in fear of pain in the healthy state using gray matter volume - Xiaowan Wang; Chris Baeken; Mengxia Fang; Jiang Qiu; Hong Chen; Guo-Rong Wu (Brain Imaging and Behavior, 2019)

Skin test of tuberculin purified protein derivatives with a dissolving microneedle-array patch - Wei Wang; Hou Ming Liu; Jing Zhou; Yu Guang Wang; Xi Feng; Hao Tang; Qinying Yan; Rong Sheng Zhu; Yu Wei Wu; Xing Guo Wang; Dan He; Fan Chen (Drug Delivery and Translational Research, 2019)

Abnormal dynamics of functional connectivity density in children with benign epilepsy with centrotemporal spikes - Rong Li; Liangcheng Wang; Heng Chen; Xiaonan Guo; Wei Liao; Ye-Lei Tang; Huafu Chen (Brain Imaging and Behavior, 2019)

Cloud Radiative Feedbacks during the ENSO Cycle Simulated by CAMS-CSM - Lin Chen; Lijuan Hua; Xinyao Rong; Jian Li; Lu Wang; Guo Zhang; Ming Sun; Zi’an Ge (Journal of Meteorological Research, 2019)

Geological and geochemical characteristics of the Baogudi Carlin-type gold district (Southwest Guizhou, China) and their geological implications - Songtao Li; Yong Xia; Jianzhong Liu; Zhuojun Xie; Qinping Tan; Yimeng Zhao; Minghua Meng; Lijin Tan; Rong Nie; Zepeng Wang; Guanghong Zhou; Haiyan Guo (Acta Geochimica, 2019)

New pyrazinoquinazoline alkaloids Isolated from a culture of Stenotrophomonas maltophilia QB-77 - Sheng-Yan Qian; Cai-Ling Yang; Afsar Khan; Rong-Xiang Chen; Ming-Song Wu; Li Tuo; Qian Wang; Jian-Guo Liu; Gui-Guang Cheng (Natural Product Research, 2019)

Two new benzophenones and one new natural amide alkaloid isolated from a mangrove-derived Fungus Penicillium citrinum - Cai-Juan Zheng; Hai-Xia Liao; Rong-Qing Mei; Guo-Lei Huang; Lu-Jia Yang; Xue-Ming Zhou; Tai-Ming Shao; Guang-Ying Chen; Chang-Yun Wang (Natural Product Research, 2019)

Chronic stress impairs the aquaporin-4-mediated glymphatic transport through glucocorticoid signaling - Fang Wei; Jian Song; Cui Zhang; Jun Lin; Rong Xue; Li-Dong Shan; Shan Gong; Guo-Xing Zhang; Zheng-Hong Qin; Guang-Yin Xu; Lin-Hui Wang (Psychopharmacology, 2019)

RETRACTED ARTICLE: Ambient air pollution and adverse birth outcomes: a systematic review and meta-analysis - Le-Qian Guo; Yu Chen; Bai-Bing Mi; Shao-Nong Dang; Dou-Dou Zhao; Rong Liu; Hong-Li Wang; Hong Yan (Journal of Zhejiang University-SCIENCE B, 2019)

An Assessment of ENSO Stability in CAMS Climate System Model Simulations - Lijuan Hua; Lin Chen; Xinyao Rong; Jian Li; Guo Zhang; Lu Wang (Journal of Meteorological Research, 2019)

A new benzofuran from the heartwood of Dalbergia latifolia - Rong-Hua Liu; Dan-Yi Mei; Shuai Lin; Ding-Qing Wang; Feng Shao; Lan-Ying Chen; Shan-Liang Guo (Natural Product Research, 2019)

Insights into the effect of chemical treatment on the physicochemical characteristics and adsorption behavior of pig manure-derived biochars - Rong-Zhong Wang; Dan-Lian Huang; Chen Zhang; Yun-Guo Liu; Guang-Ming Zeng; Cui Lai; Xiao-Min Gong; Min Cheng; Jia Wan; Qing Zhang (Environmental Science and Pollution Research, 2019)

Grey Matter Volumes in the Executive Attention System Predict Individual Differences in Effortful Control in Young Adults - Luqing Wei; Nana Guo; Chris Baeken; Minghua Bi; Xiaowan Wang; Jiang Qiu; Guo-Rong Wu (Brain Topography, 2019)

Hyperspectral discrimination of foliar biotic damages in rice using principal component analysis and probabilistic neural network - Zhan-Yu Liu; Jia-Guo Qi; Nan-Nan Wang; Zeng-Rong Zhu; Ju Luo; Li-Juan Liu; Jian Tang; Jia-An Cheng (Precision Agriculture, 2018)

Nutrient Balancing by Captive Golden Snub-Nosed Monkeys (Rhinopithecus roxellana) - Stephanie T. Chen; Xi Luo; Rong Hou; David Raubenheimer; Weihong Ji; Xuelin Jin; Zhi Jiang; Xuewei Yu; Jiajia Wang; Min Li; Songtao Guo; Baoguo Li (International Journal of Primatology, 2018)

Increased productivity of l-2-aminobutyric acid and total turnover number of NAD+/NADH in a one-pot system through enhanced thermostability of l-threonine deaminase - Ying Wang; Guo-Si Li; Pei Qiao; Ling Lin; Hai-Long Xue; Li Zhu; Mian-Bin Wu; Jian-Ping Lin; Li-Rong Yang (Biotechnology Letters, 2018)

Selective and novel cyclin-dependent kinases 4 inhibitor: synthesis and biological evaluation - Qingxiang Guo; Yongtao Li; Chao Zhang; Zhi Huang; Xin Wang; Yongwei Nie; Yao Li; Yanhua Liu; Shengyong Yang; Rong Xiang; Yan Fan (Medicinal Chemistry Research, 2018)

Agrobacterium tumefaciens-mediated transformation system for the important medicinal plant Dendrobium catenatum Lindl - Ji Chen; Li Wang; Jianbin Chen; Jin Huang; Fan Liu; Rong Guo; Li Yang; Aby Grabon; Ke Zhao; Fanlei Kong; Chen Liu; Mengliang Tian (In Vitro Cellular & Developmental Biology - Plant, 2018)

Repetitive transcranial magnetic stimulation inhibits Sirt1/MAO-A signaling in the prefrontal cortex in a rat model of depression and cortex-derived astrocytes - Zheng-wu Peng; Fen Xue; Cui-hong Zhou; Rui-guo Zhang; Ying Wang; Ling Liu; Han-fei Sang; Hua-ning Wang; Qing-rong Tan (Molecular and Cellular Biochemistry, 2018)

AMPKα inactivation destabilizes atherosclerotic plaque in streptozotocin-induced diabetic mice through AP-2α/miRNA-124 axis - Wen-Jing Liang; Sheng-Nan Zhou; Mei-Rong Shan; Xue-Qin Wang; Miao Zhang; Yuan Chen; Yun Zhang; Shuang-Xi Wang; Tao Guo (Journal of Molecular Medicine, 2018)

TNF-α/TNFR1 Signaling is Required for the Full Expression of Acute and Chronic Itch in Mice via Peripheral and Central Mechanisms - Xiuhua Miao; Ya Huang; Teng-Teng Liu; Ran Guo; Bing Wang; Xue-Long Wang; Li-Hua Chen; Yan Zhou; Ru-Rong Ji; Tong Liu (Neuroscience Bulletin, 2018)

Ionizing Radiation Blocks Hair Cell Regeneration in Zebrafish Lateral Line Neuromasts by Preventing Wnt Signaling - Rong Li; Guixiang Liao; Guo Yin; Baiyao Wang; Miaohong Yan; Xiaoshan Lin; Wenqing Zhang; Xiaohui Chen; Shasha Du; Yawei Yuan (Molecular Neurobiology, 2018)

Design, synthesis and biological evaluation of phenylpicolinamide sorafenib derivatives as antitumor agents - Chunjiang Wu; Shan Xu; Yuping Guo; Jielian Wu; Rong Luo; Wenhui Wang; Yuanbiao Tu; Le Chen; Wufu Zhu; Pengwu Zheng (Medicinal Chemistry Research, 2018)

Fiber-type distribution and expression of myosin heavy chain isoforms in newborn heterozygous myostatin-knockout pigs - Xiao-Xu Xing; Mei-Fu Xuan; Long Jin; Qing Guo; Zhao-Bo Luo; Jun-Xia Wang; Qi-Rong Luo; Guang-Lei Zhang; Cheng-Du Cui; Zheng-Yun Cui; Jin-Dan Kang; Xi-Jun Yin (Biotechnology Letters, 2017)

Improved application of tribenuron-methyl as a chemical hybridizing agent with forchlorfenuron for rapeseed hybrid breeding - Yong-Hong Li; Dian-Rong Li; Wu-Sheng Liang; Jian-Hua Tian; Jian-Chang Li; Hao Wang; Mao-Teng Li; Xu-Peng Guo; Wen-Jie Chen; Zhen-Lan Zhang; Fei Mao; Wei-Guo Zhao (Euphytica, 2017)

Protodioscin ameliorates oxidative stress, inflammation and histology outcome in Complete Freund’s adjuvant induced arthritis rats - Jia-Yu Liu; Ya-Ling Hou; Rong Cao; Hong Xia Qiu; Guo-Hua Cheng; Ran Tu; Li Wang; Jun-Li Zhang; Dan Liu (Apoptosis, 2017)

Injectable Sustained-Release Depots of PLGA Microspheres for Insoluble Drugs Prepared by hot-Melt Extrusion - Yuting Guo; Yunning Yang; Luying He; Rong Sun; Chenguang Pu; Bin Xie; Haibing He; Yu Zhang; Tian Yin; Yanjiao Wang; Xing Tang (Pharmaceutical Research, 2017)

Attenuation of β-Amyloid Toxicity In Vitro and In Vivo by Accelerated Aggregation - Aihua Yang; Chenxuan Wang; Baomin Song; Wendi Zhang; Yuanyuan Guo; Rong Yang; Guangjun Nie; Yanlian Yang; Chen Wang (Neuroscience Bulletin, 2017)

CDK inhibitor SU9516 induces tetraploid blastocyst formation from parthenogenetically activated porcine embryos - Qing Guo; Long Jin; Hai-Ying Zhu; Xiao-Chen Li; Yu-Chen Zhang; Xiao-Xu Xing; Guang-Lei Zhang; Mei-Fu Xuan; Qi-Rong Luo; Zhao-Bo Luo; Jun-Xia Wang; Jin-Dan Kang; et al. (Biotechnology Letters, 2017)

Temporal changes in wetland plant communities with decades of cumulative water pollution in two plateau lakes in China’s Yunnan Province - Si-hai Wang; Chao Wu; De-rong Xiao; Juan Wang; Xi-ping Cheng; Fang-bin Guo (Journal of Mountain Science, 2017)

Abnormal Effective Connectivity in the Brain is Involved in Auditory Verbal Hallucinations in Schizophrenia - Baojuan Li; Long-Biao Cui; Yi-Bin Xi; Karl J. Friston; Fan Guo; Hua-Ning Wang; Lin-Chuan Zhang; Yuan-Han Bai; Qing-Rong Tan; Hong Yin; Hongbing Lu (Neuroscience Bulletin, 2017)

Characterization of a Gallid herpesvirus 2 strain with novel reticuloendotheliosis virus long terminal repeat inserts - Yan-ping Zhang; Ke-yan Bao; Guo-rong Sun; Hong-chao Lv; Hong-yu Cui; Yu-long Gao; Xiao-mei Wang; Chang-jun Liu (Virus Genes, 2017)

NaCl stress induces CsSAMs gene expression in Cucumis sativus by mediating the binding of CsGT-3b to the GT-1 element within the CsSAMs promoter - Li-Wei Wang; Mei-Wen He; Shi-Rong Guo; Min Zhong; Sheng Shu; Jin Sun (Planta, 2017)

Characterizing land displacement in complex hydrogeological and geological settings: a case study in the Beijing Plain, China - Yongyong Li; Huili Gong; Lin Zhu; Xiaojuan Li; Rong Wang; Gaoxuan Guo (Natural Hazards, 2017)

RepSox improves viability and regulates gene expression in rhesus monkey–pig interspecies cloned embryos - Hai-Ying Zhu; Long Jin; Qing Guo; Zhao-Bo Luo; Xiao-Chen Li; Yu-Chen Zhang; Xiao-Xu Xing; Mei-Fu Xuan; Guang-Lei Zhang; Qi-Rong Luo; Jun-Xia Wang; Cheng-Du Cui; et al. (Biotechnology Letters, 2017)

Use of electroacupuncture and transcutaneous electrical acupoint stimulation in reproductive medicine: a group consensus - Fan Qu; Rong Li; Wei Sun; Ge Lin; Rong Zhang; Jing Yang; Li Tian; Guo-gang Xing; Hui Jiang; Fei Gong; Xiao-yan Liang; Yan Meng; et al. (Journal of Zhejiang University-SCIENCE B, 2017)

Molecular characterization of HOXC8 gene and methylation status analysis of its exon 1 associated with the length of cashmere fiber in Liaoning cashmere goat - Wen L. Bai; Jiao J. Wang; Rong H. Yin; Yun L. Dang; Ze Y. Wang; Yu B. Zhu; Yu Y. Cong; Liang Deng; Dan Guo; Shi Q. Wang; Shu H. Yang; Hui L. Xue (Genetica, 2017)

The developmental competence of oocytes parthenogenetically activated by an electric pulse and anisomycin treatment - Yu-Chen Zhang; Long Jin; Hai-Ying Zhu; Qing Guo; Xiao-Chen Li; Guang-Lei Zhang; Xiao-Xu Xing; Mei-Fu Xuan; Qi-Rong Luo; Zhao-Bo Luo; Jun-Xia Wang; Cheng-Du Cui; et al. (Biotechnology Letters, 2017)

Tenuigenin promotes the osteogenic differentiation of bone mesenchymal stem cells in vitro and in vivo - Hua-ji Jiang; Xing-gui Tian; Shou-bin Huang; Guo-rong Chen; Min-jun Huang; Yu-hui Chen; Bin Yan; Sheng-fa Li; Jia-jun Tang; Hui-yu Zhao; Liang Wang; Zhong-min Zhang (Cell and Tissue Research, 2017)

Stability analysis of slope in strain-softening soils using local arc-length solution scheme - Xiang-rong Wang; Qi-guo Rong; Shu-li Sun; Hui Wang (Journal of Mountain Science, 2017)

Neurofibromin Regulates Seizure Attacks in the Rat Pilocarpine-Induced Model of Epilepsy - Min Ren; Kunyi Li; Dan Wang; Jiamei Guo; Jing Li; Guang Yang; Xianghua Long; Wenjing Shen; Rong Hu; Xuefeng Wang; Kebin Zeng (Molecular Neurobiology, 2016)

Metastasis associated genomic aberrations in stage II rectal cancer - Hong Zhao; Zhi-Zhou Shi; Rui Jiang; Dong-Bing Zhao; Hai-Tao Zhou; Jian-Wei Liang; Xin-Yu Bi; Jian-Jun Zhao; Zhi-Yu Li; Jian-Guo Zhou; Zhen Huang; Ye-Fan Zhang; et al. (Genes & Genomics, 2016)

Experimental Study of Coal and Gas Outbursts Related to Gas-Enriched Areas - Qingyi Tu; Yuanping Cheng; Pinkun Guo; Jingyu Jiang; Liang Wang; Rong Zhang (Rock Mechanics and Rock Engineering, 2016)

The Roles of Genes in the Neuronal Migration and Neurite Outgrowth Network in Developmental Dyslexia: Single- and Multiple-Risk Genetic Variants - Shanshan Shao; Rui Kong; Li Zou; Rong Zhong; Jiao Lou; Jie Zhou; Shengnan Guo; Jia Wang; Xiaohui Zhang; Jiajia Zhang; Ranran Song (Molecular Neurobiology, 2016)

Molecular characterization, expression and methylation status analysis of BMP4 gene in skin tissue of Liaoning cashmere goat during hair follicle cycle - Wen L. Bai; Yun L. Dang; Jiao J. Wang; Rong H. Yin; Ze Y. Wang; Yu B. Zhu; Yu Y. Cong; Hui L. Xue; Liang Deng; Dan Guo; Shi Q. Wang; Shu H. Yang (Genetica, 2016)

Heat shock protein 70 inhibits cardiomyocyte necroptosis through repressing autophagy in myocardial ischemia/reperfusion injury - Xiaojuan Liu; Chao Zhang; Chi Zhang; Jingjing Li; Wanwan Guo; Daliang Yan; Chen Yang; Jianhua Zhao; Tian Xia; Yuqing Wang; Rong Xu; Xiang Wu; et al. (In Vitro Cellular & Developmental Biology - Animal, 2016)

The strong El Niño of 2015/16 and its dominant impacts on global and China's climate - Panmao Zhai; Rong Yu; Yanjun Guo; Qingxiang Li; Xuejuan Ren; Yaqiang Wang; Wenhui Xu; Yanju Liu; Yihui Ding (Journal of Meteorological Research, 2016)

Serological survey of avian influenza virus infection in non-avian wildlife in Xinjiang, China - Yu-Rong Wei; Xue-Yun Yang; Yuan-Guo Li; Jie Wei; Wen-Ge Ma; Zhi-Guang Ren; Hui-Ling Guo; Tie-Cheng Wang; Xiao-Yun Mi; Gulizhati Adili; Shu-Kui Miao; Ayiqiaolifan Shaha; et al. (Archives of Virology, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Downregulation of ubiquitin-specific protease 14 (USP14) inhibits breast cancer cell proliferation and metastasis, but promotes apoptosis - Lianxin Zhu; Shuyun Yang; Song He; Fulin Qiang; Jing Cai; Rong Liu; Changjiang Gu; Zengya Guo; Chen Wang; Wei Zhang; Chunhui Zhang; Yingying Wang (Journal of Molecular Histology, 2016)

Microbial community characteristics during simultaneous nitrification-denitrification process: effect of COD/TP ratio - Jian Zhang; Wenlin Jia; Rong Wang; Huu Hao Ngo; Wenshan Guo; Huijun Xie; Shuang Liang (Environmental Science and Pollution Research, 2016)

Lentibacillus amyloliquefaciens sp. nov., a halophilic bacterium isolated from saline sediment sample - Jing-Li Wang; Ke-Dong Ma; Yan-Wei Wang; Hui-Min Wang; Yan-Bin Li; Shan Zhou; Xiao-Rong Chen; De-Long Kong; Xiang Guo; Ming-Xiong He; Zhi-Yong Ruan (Antonie van Leeuwenhoek, 2016)

Angiotensin II increases secreted frizzled-related protein 5 (sFRP5) expression through AT1 receptor/Rho/ROCK1/JNK signaling in cardiomyocytes - Xin Jin; Bingyan Guo; Jie Yan; Rong Yang; Liang Chang; Yaling Wang; Chenglong Miao; Suyun Liu; Hui Zhang; Yongjun Li (Molecular and Cellular Biochemistry, 2015)

Ecotoxicity of two organophosphate pesticides chlorpyrifos and dichlorvos on non-targeting cyanobacteria Microcystis wesenbergii - Kai-Feng Sun; Xiang-Rong Xu; Shun-Shan Duan; You-Shao Wang; Hao Cheng; Zai-Wang Zhang; Guang-Jie Zhou; Yi-Guo Hong (Ecotoxicology, 2015)

Heavy metals in wild marine fish from South China Sea: levels, tissue- and species-specific accumulation and potential risk to humans - Jin-Ling Liu; Xiang-Rong Xu; Zhen-Hua Ding; Jia-Xi Peng; Ming-Hua Jin; You-Shao Wang; Yi-Guo Hong; Wei-Zhong Yue (Ecotoxicology, 2015)

ATF6 pathway of unfolded protein response mediates advanced oxidation protein product-induced hypertrophy and epithelial-to-mesenchymal transition in HK-2 cells - Xun Tang; Xiujie Liang; Minhui Li; Tingting Guo; Na Duan; Yue Wang; Guang Rong; Lei Yang; Shaojie Zhang; Jun Zhang (Molecular and Cellular Biochemistry, 2015)

Advanced oxidation protein products induce apoptosis in podocytes through induction of endoplasmic reticulum stress - Guang Rong; Xun Tang; Tingting Guo; Na Duan; Yue Wang; Lei Yang; Jun Zhang; Xiujie Liang (Journal of Physiology and Biochemistry, 2015)

Paenibacillus populi sp. nov., a novel bacterium isolated from the rhizosphere of Populus alba - Tong-Yan Han; Xiao-Mei Tong; Yan-Wei Wang; Hui-Min Wang; Xiao-Rong Chen; De-Long Kong; Xiang Guo; Zhi-Yong Ruan (Antonie van Leeuwenhoek, 2015)

Schwann cells induce Proliferation and Migration of Oligodendrocyte Precursor Cells Through Secretion of PDGF-AA and FGF-2 - Yue-Juan Chen; Jing-Xing Zhang; Lin Shen; Qi Qi; Xiao-Xin Cheng; Zheng-Rong Zhong; Zhi-Quan Jiang; Rui Wang; He-Zuo Lü; Jian-Guo Hu (Journal of Molecular Neuroscience, 2015)

Genetic diversity revealed by morphological traits and ISSR markers in 48 Okras (Abelmoschus escullentus L.) - Cong-Ying Yuan; Ping Wang; Pang-Pang Chen; Wen-Jun Xiao; Cheng Zhang; Shuai Hu; Ping Zhou; Hong-Ping Chang; Zhuang He; Rong Hu; Xiu-Tao Lu; Jia-Zhuo Ye; et al. (Physiology and Molecular Biology of Plants, 2015)

Spiculisporic acid analogues of the marine-derived fungus, Aspergillus candidus strain HDf2, and their antibacterial activity - Rong Wang; Zhi Kai Guo; Xiang Min Li; Fu Xiao Chen; Xia Fei Zhan; Ming Hui Shen (Antonie van Leeuwenhoek, 2015)

Molecular cloning, characterization and expression of the energy homeostasis-associated gene in piglet - Sheng-ping Wang; Yun-ling Gao; Gang Liu; Dun Deng; Rong-jun Chen; Yu-zhe Zhang; Li-li Li; Qing-qi Wen; Yong-qing Hou; Ze-meng Feng; Zhao-hui Guo (Journal of Zhejiang University-SCIENCE B, 2015)

Paenibacillus vini sp. nov., isolated from alcohol fermentation pit mud in Sichuan Province, China - Xiao-Rong Chen; Cheng-Bin Shao; Yan-Wei Wang; Ming-Xiong He; Ke-Dong Ma; Hui-Min Wang; De-Long Kong; Xiang Guo; Yi-Qing Zhou; Zhi-Yong Ruan (Antonie van Leeuwenhoek, 2015)

Determination of tumorigenic Agrobacterium density in soil by real-time PCR assay and its effect on crown gall disease severity - Qian Li; Rong-Jun Guo; Shi-Dong Li; Shi-Fang Li; Hong-Qing Wang (European Journal of Plant Pathology, 2015)

Application of molecularly imprinted polymers in wastewater treatment: a review - Dan-Lian Huang; Rong-Zhong Wang; Yun-Guo Liu; Guang-Ming Zeng; Cui Lai; Piao Xu; Bing-An Lu; Juan-Juan Xu; Cong Wang; Chao Huang (Environmental Science and Pollution Research, 2015)

Signals induced by exogenous nitric oxide and their role in controlling brown rot disease caused by Monilinia fructicola in postharvest peach fruit - Jing Ying Shi; Na Liu; Rong Xin Gu; Li Qin Zhu; Chang Zhang; Qing Guo Wang; Zhong Hua Lei; Yun Yun Liu; Ji Yun Ren (Journal of General Plant Pathology, 2015)

Characterization and molecular mapping of stripe rust resistance gene Yr61 in winter wheat cultivar Pindong 34 - X. L. Zhou; D. J. Han; X. M. Chen; H. L. Gou; S. J. Guo; L. Rong; Q. L. Wang; L. L. Huang; Z. S. Kang (Theoretical and Applied Genetics, 2014)

Effect of two-linked mutations of the FMO3 gene on itopride metabolism in Chinese healthy volunteers - Li-Ping Zhou; Zhi-Rong Tan; Hao Chen; Dong Guo; Yao Chen; Wei-Hua Huang; Lian-Sheng Wang; Guo-Gang Zhang (European Journal of Clinical Pharmacology, 2014)

Anti-apoptosis effect of polysaccharide isolated from the seeds of Cuscuta chinensis Lam on cardiomyocytes in aging rats - Shou-Li Sun; Li Guo; Ya-Chao Ren; Bing Wang; Rong-Hui Li; Yu-Shan Qi; Hui Yu; Nai-Dan Chang; Ming-Hui Li; Hai-Sheng Peng (Molecular Biology Reports, 2014)

The cellular community in the intestine of the shrimp Penaeus penicillatus and its culture environments - Chun-zhong Wang; Guo-rong Lin; Tao Yan; Zhi-peng Zheng; Bin Chen; Fu-lin Sun (Fisheries Science, 2014)

Knockdown of LYRM1 Rescues Insulin Resistance and Mitochondrial Dysfunction Induced by FCCP in 3T3-L1 Adipocytes - Min Zhang; Zhen-Ying Qin; Yong-mei Dai; Yu-Mei Wang; Guan-zhong Zhu; Ya-Ping Zhao; Chen-Bo Ji; Jin-Gai Zhu; Chun-Mei Shi; Jie Qiu; Xin-Guo Cao; Xi-Rong Guo (Cell Biochemistry and Biophysics, 2014)

The checkpoint 1 kinase inhibitor LY2603618 induces cell cycle arrest, DNA damage response and autophagy in cancer cells - Feng-Ze Wang; Hong-rong Fei; Ying-Jie Cui; Ying-Kun Sun; Zhao-Mei Li; Xue-Ying Wang; Xiao-Yi Yang; Ji-Guo Zhang; Bao-Liang Sun (Apoptosis, 2014)

Two new bicyclic sesquiterpenes from the stems of Kadsura heteroclita - Wei Su; Jian-Ping Zhao; Jian Hu; Min Yang; Melissa Jacob; Xiong Cai; Rong Zeng; Sheng-Huang Chen; Hui-Yong Huang; Ikhlas Khan; De-An Guo; Wei Wang (Natural Product Research, 2014)

Isolation and characterization of twenty-three polymorphic microsatellite loci in Schizothorax macropogon - Xiang-Zhao Guo; Gui-Rong Zhang; Ruo-Jin Yan; Wei Ji; Rui-Bin Yang; Kai-Jian Wei; Deng-Qiang Wang (Conservation Genetics Resources, 2014)

Sphingomonas gimensis sp. nov., a novel Gram-negative bacterium isolated from abandoned lead–zinc ore mine - Guang-Da Feng; Song-Zhen Yang; Yong-Hong Wang; Guo-Zhen Zhao; Ming-Rong Deng; Hong-Hui Zhu (Antonie van Leeuwenhoek, 2014)

Electrosprayed Microparticles with Loaded pDNA-Calcium Phosphate Nanoparticles to Promote the Regeneration of Mature Blood Vessels - Xueqin Guo; Tian Xia; Huan Wang; Fang Chen; Rong Cheng; Xiaoming Luo; Xiaohong Li (Pharmaceutical Research, 2014)

Analyzing and modeling rheological behavior of liver fibrosis in rats using shear viscoelastic moduli - Ying Zhu; Yi Zheng; Yuan-yuan Shen; Xin Chen; Xin-yu Zhang; Hao-ming Lin; Yan-rong Guo; Tian-fu Wang; Si-ping Chen (Journal of Zhejiang University-SCIENCE B, 2014)

Cloning and characterization of squalene synthase gene from Poria cocos and its up-regulation by methyl jasmonate - Jian-Rong Wang; Jun-Fang Lin; Li-Qiong Guo; Lin-Feng You; Xian-Lu Zeng; Jia-Ming Wen (World Journal of Microbiology and Biotechnology, 2014)

Co-expression of the Arabidopsis SOS genes enhances salt tolerance in transgenic tall fescue (Festuca arundinacea Schreb.) - Dong-Mei Ma; Wei-Rong Xu; Hui-Wen Li; Feng-Xia Jin; Ling-Na Guo; Jing Wang; Hong-Jun Dai; Xing Xu (Protoplasma, 2014)

Determination of Concentration of Methotrexate Enantiomers in Intracellular and Extracellular Fluids of HepG2 Cells by Liquid Chromatography–Tandem Mass Spectrometry - Rong Wang; Lifang Guo; Hua Xie; Juanhong Zhang; Xiaoyun Li; Wenbing Li; Jianfeng Wang; Xiaoyu Wu; Zhengping Jia (Cell Biochemistry and Biophysics, 2013)

Identification of miR-221 and -222 as important regulators in genotype IV swine hepatitis E virus ORF3-expressing HEK 293 cells - Ying Cheng; Li Du; Qiaoyun Shi; Hanwei Jiao; Xiaoru Zhang; Yongchang Hao; Hui Rong; Jianing Zhang; Xiaoxiao Jia; Shiyu Guo; Wenhua Kuang; Hui Zhang; et al. (Virus Genes, 2013)

Secretory/releasing proteome-based identification of plasma biomarkers in HBV-associated hepatocellular carcinoma - Lei Yang; WeiQi Rong; Ting Xiao; Ying Zhang; Bin Xu; Yu Liu; LiMing Wang; Fan Wu; Jun Qi; XiuYing Zhao; HongXia Wang; NaiJun Han; et al. (Science China Life Sciences, 2013)

Exome Sequencing Identified NRG3 as a Novel Susceptible Gene of Hirschsprung’s Disease in a Chinese Population - Jun Yang; Shengyu Duan; Rong Zhong; Jieyun Yin; Jiarui Pu; Juntao Ke; Xuzai Lu; Li Zou; Hongmei Zhang; Zhidong Zhu; Depeng Wang; Huasheng Xiao; et al. (Molecular Neurobiology, 2013)

Influence of ORM1 polymorphisms on the maintenance stable warfarin dosage - Lian Sheng Wang; Jing Jing Shang; Shu Ya Shi; Yan Qing Zhang; Jian Lin; Zhi Hua Guo; Yi Chen Wang; Jie Tang; Jie Liu; Ying Zi Liu; Zhi Li; Zhi Rong Tan; et al. (European Journal of Clinical Pharmacology, 2013)

Polymorphisms of UGT1A9 and UGT2B7 influence the pharmacokinetics of mycophenolic acid after a single oral dose in healthy Chinese volunteers - Dong Guo; Liang-Fang Pang; Yang Han; Hong Yang; Guo Wang; Zhi-rong Tan; Wei Zhang; Hong-Hao Zhou (European Journal of Clinical Pharmacology, 2013)

Comparison of metabolic effects of ziprasidone versus olanzapine treatment in patients with first-episode schizophrenia - Jian-Jun Ou; Yi Xu; Hong-Hui Chen; Xiaoduo Fan; Keming Gao; Juan Wang; Xiao-Feng Guo; Ren-Rong Wu; Jing-Ping Zhao (Psychopharmacology, 2013)

MiR-26a regulates cell cycle and anoikis of human esophageal adenocarcinoma cells through Rb1-E2F1 signaling pathway - Ya-Fei Zhang; An-Ran Zhang; Bi-Cheng Zhang; Zhi-Guo Rao; Jian-Fei Gao; Mu-Han Lv; Yu-Yun Wu; Su-Min Wang; Rong-Quan Wang; Dian-Chun Fang (Molecular Biology Reports, 2013)

Effect of NaCl treatments on glucosinolate metabolism in broccoli sprouts - Rong-fang Guo; Gao-feng Yuan; Qiao-mei Wang (Journal of Zhejiang University-SCIENCE B, 2013)

Paroxetine up-regulates neurogenesis in hippocampus-derived neural stem cell from fetal rats - Zheng-wu Peng; Fen Xue; Hua-ning Wang; Rui-guo Zhang; Yun-chun Chen; Ying Wang; Li-yi Zhang; Juan Fan; Qing-rong Tan (Molecular and Cellular Biochemistry, 2013)

Association between mandibular posterior alveolar morphology and growth pattern in a Chinese population with normal occlusion - Min Han; Rong-yang Wang; Hong Liu; Xiu-juan Zhu; Fu-lan Wei; Tao Lv; Na-na Wang; Li-hua Hu; Guo-ju Li; Dong-xu Liu; Chun-ling Wang (Journal of Zhejiang University-SCIENCE B, 2013)

The Diagnostic Value of Treadmill Exercise Test Parameters for Coronary Artery Disease - Jian Ling Sun; Rong Han; Ji Hong Guo; Xiao Ying Li; Xian Lin Ma; Chong Yu Wang (Cell Biochemistry and Biophysics, 2013)

Volatile profile analysis and quality prediction of Longjing tea (Camellia sinensis) by HS-SPME/GC-MS - Jie Lin; Yi Dai; Ya-nan Guo; Hai-rong Xu; Xiao-chang Wang (Journal of Zhejiang University-SCIENCE B, 2012)

Effects of Ibutilide on Canine Cardiac Pacing Threshold and on Induction Rates of Atrial Fibrillation - Jian-ling Sun; Rong Han; Ji-hong Guo; Xiao-ying Li; Xian-lin Ma; Chong-yu Wang (Cell Biochemistry and Biophysics, 2012)

Simple and rapid detection of swine hepatitis E virus by reverse transcription loop-mediated isothermal amplification - Liang-Quan Zhang; Fu-Rong Zhao; Zhi-Gang Liu; Wei-Li Kong; Heng Wang; Yun Ouyang; Huan-Bin Liang; Chao-Yi Zhang; Hai-Tao Qi; Chang-Li Huang; Si-Hu Guo; Gui-Hong Zhang (Archives of Virology, 2012)

Oxidative Parameters in the Rat Brain of Chronic Mild Stress Model for Depression: Relation to Anhedonia-Like Responses - Chao Wang; He-ming Wu; Xiao-rong Jing; Qiang Meng; Bei Liu; Hua Zhang; Guo-dong Gao (The Journal of Membrane Biology, 2012)

Effect of Ibutilide on the Canine Cardiac Conduction System - Jian Ling Sun; Rong Han; Ji Hong Guo; Xiao Ying Li; Xian Lin Ma; Chong Yu Wang (Cell Biochemistry and Biophysics, 2012)

A molecular mechanism underlying ovarian dysfunction of polycystic ovary syndrome: hyperandrogenism induces epigenetic alterations in the granulosa cells - Fan Qu; Fang-Fang Wang; Rong Yin; Guo-Lian Ding; Mohamed El-prince; Qian Gao; Bi-Wei Shi; Hui-Hui Pan; Yi-Ting Huang; Min Jin; Peter C. K. Leung; Jian-Zhong Sheng; et al. (Journal of Molecular Medicine, 2012)

Proteomic analysis of the nuclear phosphorylated proteins in dairy cow mammary epithelial cells treated with estrogen - Jian-guo Huang; Xue-jun Gao; Qing-zhang Li; Li-min Lu; Rong Liu; Chao-chao Luo; Jia-li Wang; Qiao Bin; Xin Jin (In Vitro Cellular & Developmental Biology - Animal, 2012)

At-line monitoring of key parameters of nisin fermentation by near infrared spectroscopy, chemometric modeling and model improvement - Wei-Liang Guo; Yi-Ping Du; Yong-Can Zhou; Shuang Yang; Jia-Hui Lu; Hong-Yu Zhao; Yao Wang; Li-Rong Teng (World Journal of Microbiology and Biotechnology, 2012)

Imprinting analysis of porcine MAGEL2 gene in two fetal stages and association analysis with carcass traits - Ling Guo; Mu Qiao; Chao Wang; Rong Zheng; Yuan-Zhu Xiong; Chang-Yan Deng (Molecular Biology Reports, 2012)

Phenotypic and molecular characterization of rhizobacterium Burkholderia sp. strain R456 antagonistic to Rhizoctonia solani, sheath blight of rice - Bin Li; Bao-Ping Liu; Rong-Rong Yu; Miao-Miao Lou; Yan-Li Wang; Guan-Lin Xie; Hong-Ye Li; Guo-Chang Sun (World Journal of Microbiology and Biotechnology, 2011)

Discovering the distinct inhibitory effects between C4-epimeric glycosyl amino acids: new insight into the development of protein tyrosine phosphatase inhibitors - Xiao-Peng He; Cui Li; Zhi-Zhou Wang; Li-Xin Gao; Xiao-Xin Shi; Yun Tang; Juan Xie; Jia Li; Guo-Rong Chen; Kaixian Chen (Glycoconjugate Journal, 2011)

Effect of dietary fatty acids on serum parameters, fatty acid compositions, and liver histology in Shaoxing laying ducks - Wei-meng Liu; Shu-jing Lai; Li-zhi Lu; Fang-xiong Shi; Jing Zhang; Yu Liu; Bo Yu; Zheng-rong Tao; Jun-da Shen; Guo-qin Li; De-qian Wang; Jin-jun Li; et al. (Journal of Zhejiang University-SCIENCE B, 2011)

M. tuberculosis H37Rv Infection of Chinese Rhesus Macaques - Jing Zhang; Yan-Qing Ye; Yong Wang; Ping-Zheng Mo; Qiao-Yang Xian; Yan Rao; Rong Bao; Ming Dai; Jun-Yan Liu; Ming Guo; Xin Wang; Zhi-Xiang Huang; et al. (Journal of Neuroimmune Pharmacology, 2011)

Mimic peptides bonding specifically with the first and second extracellular loops of the CC chemokine receptor 5 derived from a phage display peptide library are potent inhibitors of experimental autoimmune encephalomyelitis - Hui-min Zheng; Yun Jiang; Ju-rong Wang; Xue-lian Gong; Bao-yu Guo (Inflammation Research, 2011)

Combination of Hyaluronic Acid Hydrogel Scaffold and PLGA Microspheres for Supporting Survival of Neural Stem Cells - Ying Wang; Yue Teng Wei; Zhao Hui Zu; Rong Kai Ju; Mu Yao Guo; Xiu Mei Wang; Qun Yuan Xu; Fu Zhai Cui (Pharmaceutical Research, 2011)

Genistein alters caffeine exposure in healthy female volunteers - Yao Chen; Chang-Qiong Xiao; Yi-Jing He; Bi-Lian Chen; Guo Wang; Gan Zhou; Wei Zhang; Zhi-Rong Tan; Shan Cao; Li-Ping Wang; Hong-Hao Zhou (European Journal of Clinical Pharmacology, 2011)

Prognostic value of serum soluble Fas in patients with locally advanced unresectable rectal cancer receiving concurrent chemoradiotherapy - Qi-lian Liang; Zhou-yu Li; Guo-qiang Chen; Zhen-nan Lai; Bi-rong Wang; Jie Huang (Journal of Zhejiang University-SCIENCE B, 2010)

Effects of immune activation on the retrieval of spatial memory - Zhen-Bo Huang; Hao Wang; Xiu-Rong Rao; Tao Liang; Jing Xu; Xiang-Sheng Cai; Guo-Qing Sheng (Neuroscience Bulletin, 2010)

NYGGF4 homologous gene expression in 3T3-L1 adipocytes: regulation by FFA and adipokines - Ya-ping Zhao; Chun-mei Zhang; Chun Zhu; Xiao-hui Chen; Jia-lin Wang; Chen-bo Ji; Xia Chi; Qin Hong; Yu-zhu Peng; Xi-rong Guo (Molecular Biology Reports, 2010)

Effect of glycyrrhizin on the activity of CYP3A enzyme in humans - Jiang-Hua Tu; Yi-Jing He; Yao Chen; Lan Fan; Wei Zhang; Zhi-Rong Tan; Yuan-Fei Huang; Dong Guo; Dong-Li Hu; Dan Wang; Hong-Hao Zhou (European Journal of Clinical Pharmacology, 2010)

Ophiocerol, a novel macrocylic neolignan from the aquatic fungus Ophioceras dolichostomum YMF1.00988 - Jin-Yan Dong†; Le Wang†; Hong-Chuang Song; Li-Mei Wang; Kai-Ze Shen; Rong Sun; Guo-Hong Li; Lei Li; Ke-Qin Zhang (Natural Product Research, 2010)

Acid-sensing ion channel 1a mediates acid-induced increases in intracellular calcium in rat articular chondrocytes - Feng-Lai Yuan; Fei-Hu Chen; Wei-Guo Lu; Xia Li; Fan-Rong Wu; Jian-Ping Li; Cheng-Wan Li; Yu Wang; Teng-Yue Zhang; Wei Hu (Molecular and Cellular Biochemistry, 2010)

Validity and reliability testing of the Chinese (mainland) version of the 39-item Parkinson’s Disease Questionnaire (PDQ-39) - Wei Luo; Xiao-hong Gui; Bo Wang; Wen-ying Zhang; Zhi-yuan Ouyang; Yi Guo; Bao-rong Zhang; Mei-ping Ding (Journal of Zhejiang University-SCIENCE B, 2010)

New flavonoids with 2BS cell proliferation promoting effect from the seeds of Trigonella foenum-graecum L. - Guo-Rong Wang; Wen-Zhao Tang; Qing-Qiang Yao; Hao Zhong; Yong-Jun Liu (Journal of Natural Medicines, 2010)

Manganese-induced changes of the biochemical characteristics of the recombinant wild-type and mutant PrPs - Xiao-Li Li; Chen-Fang Dong; Gui-Rong Wang; Rui-Min Zhou; Qi Shi; Chan Tian; Chen Gao; Guo-Yong Mei; Cao Chen; Kun Xu; Jun Han; Xiao-Ping Dong (Medical Microbiology and Immunology, 2009)

Curcumin prevents liver fibrosis by inducing apoptosis and suppressing activation of hepatic stellate cells - Jian-Chang Shu; Ya-Jun He; Xia Lv; Guo-Rong Ye; Le-Xin Wang (Journal of Natural Medicines, 2009)

DcR3 and survivin are highly expressed in colorectal carcinoma and closely correlated to its clinicopathologic parameters - Qi-lian Liang; Bi-rong Wang; Guo-hong Li (Journal of Zhejiang University-SCIENCE B, 2009)

Temporal patterns of net soil N mineralization and nitrification through secondary succession in the subtropical forests of eastern China - En-Rong Yan; Xi-Hua Wang; Ming Guo; Qiang Zhong; Wu Zhou; Yong-Fu Li (Plant and Soil, 2009)

Effects of allicin on CYP2C19 and CYP3A4 activity in healthy volunteers with different CYP2C19 genotypes - Li-Jun Yang; Lan Fan; Zhao-Qian Liu; Yan-Mei Mao; Dong Guo; Li-Hui Liu; Zhi-Rong Tan; Liang Peng; Chun-Ting Han; Dong-Li Hu; Dan Wang; Hong-Hao Zhou (European Journal of Clinical Pharmacology, 2009)

Induction of cytochrome P450 2B6 activity by the herbal medicine baicalin as measured by bupropion hydroxylation - Lan Fan; Jin-Chao Wang; Feng Jiang; Zhi-Rong Tan; Yao Chen; Qing Li; Wei Zhang; Guo Wang; He-Ping Lei; Dong-Li Hu; Dan Wang; Hong-Hao Zhou (European Journal of Clinical Pharmacology, 2009)

The CYP2C19 ultra-rapid metabolizer genotype influences the pharmacokinetics of voriconazole in healthy male volunteers - Guo Wang; He-Ping Lei; Zhi Li; Zhi-Rong Tan; Dong Guo; Lan Fan; Yao Chen; Dong-Li Hu; Dan Wang; Hong-Hao Zhou (European Journal of Clinical Pharmacology, 2009)

An investigation on the polymorphisms of two DNA repair genes and susceptibility to ESCC and GCA of high-incidence region in northern China - Na Wang; Xiu-juan Dong; Rong-miao Zhou; Wei Guo; Xiao-juan Zhang; Yan Li (Molecular Biology Reports, 2009)

15-HETE suppresses K+ channel activity and inhibits apoptosis in pulmonary artery smooth muscle cells - Yumei Li; Qian Li; Zhigang Wang; Di Liang; Shujun Liang; Xiaobo Tang; Lei Guo; Rong Zhang; Daling Zhu (Apoptosis, 2009)

Variation of 423G>T in the Agouti Gene Exon 4 in Indigenous Chinese Goat Breeds - Chun-Juan Tang; Rong-Yan Zhou; Xiang-Long Li; Jing-Wen Zhao; Lan-Hui Li; Fu-Jun Feng; Dong-Feng Li; Jian-Tao Wang; Xiu-Li Guo; Jing-Fen Keng (Biochemical Genetics, 2008)

hBolA, novel non-classical secreted proteins, belonging to different BolA family with functional divergence - Yu-Bo Zhou; Jia-Bing Cao; Bing-Bing Wan; Xin-Rong Wang; Guo-Hui Ding; Hong Zhu; Hong-Meng Yang; Ke-Sheng Wang; Xin Zhang; Ze-Guang Han (Molecular and Cellular Biochemistry, 2008)

Isolation and identification of Sclerotinia stem rot causal pathogen in Arabidopsis thaliana - Ai-rong Wang; Wen-wei Lin; Xiao-ting Chen; Guo-dong Lu; Jie Zhou; Zong-hua Wang (Journal of Zhejiang University-SCIENCE B, 2008)

Fluorescent co-localization of PTS1 and PTS2 and its application in analysis of the gene function and the peroxisomal dynamic in Magnaporthe oryzae - Jiao-yu Wang; Xiao-yan Wu; Zhen Zhang; Xin-fa Du; Rong-yao Chai; Xiao-hong Liu; Xue-qin Mao; Hai-ping Qiu; Yan-li Wang; Fu-cheng Lin; Guo-chang Sun (Journal of Zhejiang University-SCIENCE B, 2008)

Vesicular stomatitis virus matrix protein gene enhances the antitumor effects of radiation via induction of apoptosis - Xiao-Bo Du; Jin-Yi Lang; Jian-Rong XU; You Lu; Yan-Jun Wen; Ju-Mei Zhao; Peng Diao; Zhi-Ping Yuan; Bin Yao; Ling-Yu Fan; Guo-Qing Wang; Li Liu; et al. (Apoptosis, 2008)

Expression, purification and characterization of a phyA m -phyCs fusion phytase - Li-kou Zou; Hong-ning Wang; Xin Pan; Guo-bao Tian; Zi-wen Xie; Qi Wu; Hui Chen; Tao Xie; Zhi-rong Yang (Journal of Zhejiang University-SCIENCE B, 2008)

Nematicidal coumarins from Heracleum candicans Wall. - Xing-Biao Wang¶; Guo-Hong Li¶; Lei Li; Li-Jun Zheng; Rong Huang; Ke-Qin Zhang (Natural Product Research, 2008)

Identification of defense-related genes in rice responding to challenge by Rhizoctonia solani - Chang-Jiang Zhao; Ai-Rong Wang; Yu-Jun Shi; Liu-Qing Wang; Wen-De Liu; Zong-Hua Wang; Guo-Dong Lu (Theoretical and Applied Genetics, 2008)

Polymorphisms in intron 1 of the porcinePOU1F1 gene - Cheng-Yi Song; Bo Gao; Shang-Hui Teng; Xiao-Yang Wang; Fei Xie; Guo-hong Chen; Zhi-Yue Wang; Rong-bin Jing; Jiu-De Mao (Journal of Applied Genetics, 2007)

Phytase expression in transgenic soybeans: stable transformation with a vector-less construct - Xiao Rong Gao; Guo Kun Wang; Qiao Su; Yan Wang; Li Jia An (Biotechnology Letters, 2007)

Knockout of the gene (ste15) encoding a glycosyltransferase and its function in biosynthesis of exopolysaccharide in Streptomyces sp. 139 - Qing-Li Sun; Ling-Yan Wang; Jun-Jie Shan; Rong Jiang; Lian-Hong Guo; Yang Zhang; Ren Zhang; Yuan Li (Archives of Microbiology, 2007)

Morphological changes of cholinergic nerve fibers in the urinary bladder after establishment of artificial somatic-autonomic reflex arc in rats - Han-Zhi Wang; Shu-Rong Li; Can Wen; Chuan-Guo Xiao; Bing-Yin Su (Neuroscience Bulletin, 2007)

Cytological and molecular characterization of a novel monogenic dominant GMS in Brassica napus L. - Dao-Jie Wang; Ai-Guang Guo; Dian-Rong Li; Jian-Hua Tian; Fei Huang; Gen-Lou Sun (Plant Cell Reports, 2007)

Genotypic Analysis of Multidrug-Resistant Mycobacterium tuberculosis Isolates Recovered From Central China - Shu-Lin Zhang; Hua Qi; Dun-Lian Qiu; Da-Xu Li; Jie Zhang; Chang-Mei Du; Guo-Bin Wang; Zhi-Rong Yang; Qun Sun (Biochemical Genetics, 2007)

Glucosamine sulfate–induced apoptosis in chronic myelogenous leukemia K562 cells is associated with translocation of cathepsin D and downregulation of Bcl-xL - Zhe Wang; Rong Liang; Gao-Sheng Huang; Ying Piao; Yong-Qing Zhang; Ai-Qin Wang; Bao-Xia Dong; Ji-Liang Feng; Guo-Rong Yang; Ying Guo (Apoptosis, 2006)

Crop yield, nitrogen uptake and nitrate-nitrogen accumulation in soil as affected by 23 annual applications of fertilizer and manure in the rainfed region of Northwestern China - Sheng-Mao Yang; S. S. Malhi; Jian-Rong Song; You-Cai Xiong; Wei-Yun Yue; Li Li Lu; Jian-Guo Wang; Tian-Wen Guo (Nutrient Cycling in Agroecosystems, 2006)

Conversion rates of surface HOx radicals in Beijing City - Xin-rong Ren; Li-xin Wang; Hui-xiang Wang; Guo-fang Miao (Chinese Geographical Science, 2004)

GSTP1 polymorphisms and gastric cancer in a high-risk Chinese population - Veronica Wendy Setiawan; Zuo-Feng Zhang; Guo-Pei Yu; Qing-Yi Lu; Yong-Liang Li; Ming-Lan Lu; Ming-Rong Wang; Chun Hua Guo; Shun-Zhang Yu; Robert C Kurtz; Chung-Cheng Hsieh (Cancer Causes & Control, 2001)